Composition, temporary fixing composition, and wafer manufacturing method using the temporary fixing composition

CN122936030APending Publication Date: 2026-10-16DENKA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580020476.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-14
Filing Date
2025-03-12
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0121] According to one aspect of this disclosure, a composition capable of forming a temporary fixing layer that is not easily affected by the processing technology and remains on the wafer, a temporary fixing composition, and a method for manufacturing a wafer using the same can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122936030A_ABST
    Figure CN122936030A_ABST
Patent Text Reader

Abstract

This disclosure provides a composition whose peel strength X, measured by the following method (X) using polyimide as a test substrate, is [value missing]. PI The peel strength Y is below 0.50 N / mm, measured by the following method (Y) using polyimide as the test substrate. PI The peel strength X is above 0.10 N / mm. PI Compared with the above peel strength Y PI The ratio of X PI / Y PI The peel strength is 1.5 or less. (X) The peel strength is determined by the following steps (i) to (iv). (i) The above composition is coated on a test substrate with a thickness of 70 μm, and after being bonded to a glass plate, the above composition is photocured to form a coating film. (ii) The test substrate with the above coating film is heated at 175°C for 30 minutes. (iii) The above coating film is irradiated with an energy density of 920 mJ / cm at a wavelength of 355 nm and a frequency of 40 kHz. 2 (iv) After laser treatment, the glass plate is peeled off. A peeling tape is applied to the coating, and the peel strength is measured under the following conditions: peel direction 180 degrees, peel width 20 mm, peel speed 120 mm / min, and temperature 25°C. The average value of five measurements is taken. (y) In the above measurement method (x), the peel strength is measured without performing step (ii).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to compositions, compositions for temporary fixation, and methods for manufacturing wafers using the same. Background Technology

[0002] In the manufacturing process of semiconductor devices, semiconductor substrates (hereinafter referred to as "wafers") undergo processes such as insulating film formation, circuit formation, and thinning by grinding / polishing. During the thinning process, in order to prevent wafer breakage, the wafer is sometimes bonded to a support member such as a glass plate using a temporary fixing composition, and the support member is peeled off from the wafer after a specified processing step.

[0003] For example, Patent Document 1 discloses monofunctional (meth)acrylates, polyfunctional (meth)acrylates, polyisobutylene homopolymers and / or polyisobutylene copolymers, and photoradical polymerization initiators as such temporary fixation compositions, wherein the side chains are alkyl with 18 or more carbon atoms and the Tg of the homopolymer is -100°C to 60°C.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2021 / 235406 Summary of the Invention

[0007] However, when the temporary fixing composition is peeled off the wafer, sometimes some of the cured material of the temporary fixing composition remains on the wafer surface. In addition, in wafers with patterns such as polyimide or aluminum on the surface, the degree of cured material residue will vary because the types of components exposed on the wafer surface are different and their adhesion to the temporary fixing composition is also different.

[0008] Further research revealed that even when the types of components exposed on the wafer surface are the same, the degree of cured residue can vary depending on the processing technology involved in the bonding of the wafer and the support component via a temporary fixing composition. For example, even when the type of component exposed on the wafer surface is polyimide, the degree of cured residue will differ depending on whether the processing technology involves specified heat treatment or not.

[0009] Furthermore, as types of temporary fixing compositions, there are those that are cured (bonded) by light irradiation, decomposed (peeled) by laser irradiation, cured by heat and decomposed by laser irradiation, and cured by heat and decomposed by heat. Among these, the temporary fixing compositions that are cured (bonded) by light irradiation and decomposed (peeled) by laser irradiation have the advantage of having less thermal impact on the semiconductor substrate.

[0010] However, in the first temporary fixing composition, if the bonding strength under light irradiation is improved, the peelability under laser irradiation is easily reduced, and during peeling, the cured material of the temporary fixing composition may remain on the bonding surface of the wafer. On the other hand, if the wafer bonding strength is poor, the support member may peel off during the processing steps, making it difficult to prevent wafer breakage.

[0011] This invention was made in view of the aforementioned problems and aims to solve at least one of the aforementioned issues. One object of this disclosure is to provide a composition capable of forming a temporary fixing layer that is not easily affected by processing techniques and remains on the wafer, a temporary fixing composition, and a method for manufacturing a wafer using the same. Another object of this disclosure is to provide a composition with excellent laser ablation properties, capable of forming a temporary fixing layer that is not easily left on the wafer, a temporary fixing composition, and a method for manufacturing a wafer using the same.

[0012] To achieve the above-mentioned objectives, the inventors conducted in-depth research and discovered that when a wafer is heat-treated, the adhesive force between the temporary fixing layer and the wafer increases excessively, potentially leading to residue of the temporary fixing layer. Based on this insight, the inventors found that a composition whose peel strength after heat treatment and peel strength without heat treatment meet specified conditions can solve at least one of the above-mentioned problems. For example, it is possible to provide a composition capable of forming a temporary fixing layer that is not easily affected by the processing technology and remains on the wafer, a composition for temporary fixing, and a method for manufacturing a wafer using the same, thereby completing the present invention.

[0013] Furthermore, the inventors conducted in-depth research to achieve the above objectives and found that compositions with hydrocarbon chain concentration and aromatic ring concentration within a specified range can solve at least one of the above problems. For example, they can provide a composition with excellent laser ablation properties that can form a temporary fixing layer that is not easily left on the wafer, a composition for temporary fixing, and a method for manufacturing a wafer using the same, thereby completing the present invention.

[0014] That is, this disclosure includes the following embodiments. [1]

[0016] A composition,

[0017] The peel strength X was measured by the following method (X) using polyimide as the test substrate. PI Below 0.50 N / mm

[0018] The peel strength Y was measured by the following method (Y) using polyimide as the test substrate. PI It is above 0.10 N / mm.

[0019] The above peel strength XPI Compared with the above peel strength Y PI The ratio of X PI / Y PI It is below 1.5.

[0020] (X) Determine the peel strength through the following procedures (i) to (iv).

[0021] (i) The above composition is coated on a test substrate with a thickness of 70 μm, and after being bonded to a glass plate, the composition is photocured to form a coating film.

[0022] (ii) The test substrate with the above coating film formed was heated at 175°C for 30 minutes.

[0023] (iii) The above coating was irradiated at a wavelength of 355 nm and a frequency of 40 kHz with an energy density of 920 mJ / cm². 2 After laser treatment, the glass plate is peeled off.

[0024] (iv) Apply release tape to the above coating film, and measure the peel strength when peeling the above coating film from the above test substrate under the conditions of peel direction 180 degrees, peel width 20 mm, peel speed 120 mm / min and temperature 25°C. Take the average value of 5 measurements.

[0025] (Y) In the above-described test method (X), the peel strength is measured without performing the above-described procedure (ii). [2]

[0027] According to the composition described in [1], wherein the above ratio X PI / Y PI It ranges from 0.30 to 1.0. [3]

[0029] According to the composition described in [1] or [2], wherein,

[0030] The peel strength X measured by the above-described method (X) using aluminum as the test substrate Al Below 0.60 N / mm

[0031] The peel strength Y was measured using the above-described method (Y) with aluminum as the test substrate. Al It is above 0.10 N / mm.

[0032] The above peel strength X Al Compared with the above peel strength Y Al The ratio of X Al / Y Al It is below 2.0. [4]

[0034] According to the composition described in [3], wherein the above ratio X Al / Y Al It ranges from 1.0 to 2.0. [5]

[0036] According to the composition described in [3] or [4], wherein the peel strength X is as described above. PI Compared with the above peel strength X Al The ratio of X PI / X Al The value is 0.10 to 0.50. [6]

[0038] The composition according to any one of [1] to [5], wherein,

[0039] The peel strength X measured by the above-described measurement method (X) using silicon as the test substrate Si Below 0.50 N / mm

[0040] The peel strength Y was measured using the above-described measurement method (Y) with silicon as the test substrate. Si It is above 0.10 N / mm.

[0041] The above peel strength X Si Compared with the above peel strength Y Si The ratio of X Si / Y Si It is below 1.6. [7]

[0043] According to the composition described in [6], wherein the above ratio X Si / Y Si The value ranges from 0.3 to 1.2. [8]

[0045] The composition according to any one of [1] to [7] contains polymerizable compound A and photopolymerization initiator B. [9]

[0047] According to the composition described in [8], wherein the polymeric compound A comprises:

[0048] Polymerizable compound A1 having a hydrocarbon chain with 3 or more carbon atoms, and

[0049] A2 is a polymeric compound with an aromatic ring.

[10]

[0051] According to the composition described in [9], wherein the polymeric compound A1 comprises a (meth)acrylate in which the functional group equivalent of a hydrocarbon chain having 3 or more carbon atoms is less than 200 g / mol.

[11]

[0053] According to the composition described in [9] or

[10] , wherein the polymeric compound A1 comprises a (meth)acrylate having a hydrocarbon chain having 8 or more carbon atoms.

[12]

[0055] The composition according to any one of [9] to

[11] , wherein the polymeric compound A2 comprises (meth)acrylate with an aromatic ring equivalent of less than 200 g / mol.

[13]

[0057] The composition according to any one of [9] to

[12] , wherein the content of the polymeric compound A1 is 50 to 98 parts by mass relative to the total amount of polymeric compound A, 100 parts by mass.

[14]

[0059] The composition according to any one of [9] to

[13] , wherein the content of the polymeric compound A2 is 2 to 50 parts by mass relative to the total amount of polymeric compound A, 100 parts by mass.

[15]

[0061] The composition according to any one of [8] to

[14] , wherein the content of the above-mentioned photopolymerization initiator B is 0.01 to 10 parts by mass relative to 100 parts by mass of the total amount of polymerizable compound A.

[16]

[0063] A temporary fixation composition comprising any one of [1] to

[15] .

[17]

[0065] A method for manufacturing a chip, comprising:

[0066] The process of bonding the wafer to the support member via the temporary fixing composition described in

[16] ;

[0067] The process of curing the above-mentioned temporary fixing composition by irradiating it with ultraviolet light to form a temporary fixing layer, and bonding the above-mentioned wafer to the above-mentioned support member through the above-mentioned temporary fixing layer;

[0068] The process of heat-treating the aforementioned wafer;

[0069] The process of irradiating the aforementioned temporary fixing layer with laser; and

[0070] The process of peeling the support member from the wafer at the interface of the temporary fixing layer.

[18]

[0072] According to the manufacturing method described in

[17] , the process further includes a step of removing the temporary fixing layer after laser irradiation from the wafer.

[19]

[0074] A composition, the peel strength X of which is measured by the following method (X) using polyimide as a test substrate. PI The peel strength Y, measured by the following method (Y) using polyimide as the test substrate, is compared with the peel strength Y. PI The ratio of X PI / Y PI It is below 1.5.

[0075] (X) Determine the peel strength through the following procedures (i) to (iv).

[0076] (i) The above composition is coated on a test substrate with a thickness of 70 μm, and after being bonded to a glass plate, the composition is photocured to form a coating film.

[0077] (ii) The test substrate with the above coating film formed was heated at 175°C for 30 minutes.

[0078] (iii) After irradiating the above coating with a laser with an energy density of 920 mJ / cm² at a wavelength of 355 nm and a frequency of 40 kHz, the above glass plate is peeled off.

[0079] (iv) Apply release tape to the above coating film, and measure the peel strength when peeling the above coating film from the above test substrate under the conditions of peel direction 180 degrees, peel width 20 mm, peel speed 120 mm / min and temperature 25°C. Take the average value of 5 measurements.

[0080] (Y) In the above-described test method (X), the peel strength is measured without performing the above-described procedure (ii).

[0081] [1']

[0082] A composition comprising a polymerizable compound A and a photopolymerization initiator B,

[0083] The concentration of hydrocarbon chains with 3 or more carbon atoms is above 2.80 mmol / g.

[0084] The concentration of aromatic rings is above 0.60 mmol / g.

[0085] [2']

[0086] According to the composition described in [1'], the crosslinking density of the cured product after ultraviolet irradiation is 0.10 mmol / cm². 3 above.

[0087] [3']

[0088] According to the composition described in [1'] or [2'], the ratio of the concentration of the hydrocarbon chain with 3 or more carbon atoms to the concentration of the aromatic ring is 1.5 or more.

[0089] [4']

[0090] The composition according to any one of [1'] to [3'], wherein the polymeric compound A comprises at least one selected from polymeric compound A1 having a hydrocarbon chain having 3 or more carbon atoms, polymeric compound A2 having an aromatic ring, and polymeric compound A3 having a hydrocarbon chain and an aromatic ring having 3 or more carbon atoms.

[0091] [5']

[0092] According to the composition described in [4'], for at least one of the polymeric compounds A1 and A3, there is a (meth)acrylate containing a hydrocarbon chain with a functional group equivalent of 200 g / mol or less.

[0093] [6']

[0094] The composition according to [4'] or [5'], wherein at least one of the above-mentioned polymeric compound A1 and the above-mentioned polymeric compound A3 comprises a (meth)acrylate having a hydrocarbon chain having 8 or more carbon atoms.

[0095] [7']

[0096] The composition according to any one of [4'] to [6'], wherein at least one of the above-mentioned polymeric compound A2 and polymeric compound A3 contains an aromatic ring equivalent of less than 200 g / mol of (meth)acrylate.

[0097] [8']

[0098] The composition according to any one of [4'] to [7'], wherein the content of the above-mentioned polymeric compound A1 is 50 to 98 parts by mass relative to the total amount of polymeric compound A, 100 parts by mass.

[0099] [9']

[0100] The composition according to any one of [4'] to [8'], wherein the content of the above-mentioned polymeric compound A2 is 2 to 50 parts by mass relative to the total amount of polymeric compound A 100 parts by mass.

[0101] [10']

[0102] The composition according to any one of [4'] to [9'], wherein the content of the polymeric compound A3 is 0 to 48 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

[0103] [11']

[0104] The composition according to any one of [1'] to [10'], wherein the content of the above-mentioned photopolymerization initiator B is 0.01 to 10 parts by mass relative to the total amount of polymerizable compound A (100 parts by mass).

[0105] [12']

[0106] The composition according to any one of [1'] to [11'], wherein the polymerizable compound A comprises a monofunctional polymerizable compound and a polyfunctional polymerizable compound,

[0107] The content of the above-mentioned monofunctional polymeric compounds is 0.01 to 60 parts by mass relative to the total amount of polyfunctional polymeric compounds per 100 parts by mass.

[0108] [13']

[0109] The composition according to any one of [1'] to [12'], wherein the viscosity at 23°C is 500 mPa·s to 10000 mPa·s.

[0110] [14']

[0111] A temporary fixation composition comprising any one of [1'] to [13'].

[0112] [15']

[0113] A method for manufacturing a chip, comprising:

[0114] The process of bonding a wafer to a support member via the temporary fixing composition described in [14'];

[0115] The process of curing the above-mentioned temporary fixing composition by irradiating it with ultraviolet light to form a temporary fixing layer, and bonding the above-mentioned wafer to the above-mentioned support member through the above-mentioned temporary fixing layer;

[0116] The process of processing the aforementioned wafer;

[0117] The process of irradiating the aforementioned temporary fixing layer with laser; and

[0118] The process of peeling the support member from the wafer at the interface of the temporary fixing layer.

[0119] [16']

[0120] According to the manufacturing method described in [15'], the process further includes a step of removing the temporary fixing layer after laser irradiation from the wafer.

[0121] According to one aspect of this disclosure, a composition capable of forming a temporary fixing layer that is not easily affected by the processing technology and remains on the wafer, a temporary fixing composition, and a method for manufacturing a wafer using the same can be provided.

[0122] According to one aspect of this disclosure, a composition with excellent laser ablation properties, capable of forming a temporary fixing layer that is not easily left on a wafer, a temporary fixing composition, and a method for manufacturing a wafer using the same can be provided. Attached Figure Description

[0123] Figure 1 This is an example of a flowchart showing the wafer manufacturing method of this embodiment from the thickness direction (front side) of the wafer.

[0124] Figure 2 This is another example of a flowchart showing the wafer manufacturing method of this embodiment from the thickness direction (front side) of the wafer. Detailed Implementation

[0125] Hereinafter, embodiments of the present invention (hereinafter referred to as "this embodiment") will be described in detail. However, the present invention is not limited to the following embodiments, and various modifications can be made without departing from its spirit.

[0126] In this specification, a numerical range such as "1 to 100" indicates that it includes its lower limit "1" and upper limit "100". Other numerical ranges are represented in the same way.

[0127] [First Implementation]

[0128] 1. Compositions and compositions for temporary fixation

[0129] In the composition of this embodiment, the peel strength X is measured by the following measurement method (X) using polyimide as a test substrate. PI The peel strength Y is below 0.50 N / mm, measured by the following method (Y) using polyimide as the test substrate. PI With a peel strength of 0.10 N / mm or higher, X PI With peel strength Y PI The ratio of X PI / Y PI It is below 1.5.

[0130] (X) Determine the peel strength through the following procedures (i) to (iv).

[0131] (i) The temporary fixation composition was coated on the test substrate to a thickness of 70 μm, and after the glass plate was attached, the temporary fixation composition was photocured to form a coating film.

[0132] (ii) The test substrate with the coating film formed was heated at 175°C for 30 minutes.

[0133] (iii) The coating was irradiated at a wavelength of 355 nm and a frequency of 40 kHz with an energy density of 920 mJ / cm². 2 After laser treatment, the glass plate is peeled off.

[0134] (iv) Apply release tape to the coating and measure the peel strength when peeling the coating from the test substrate under the conditions of 180° peel direction, 20 mm peel width, 120 mm / min peel speed and 25°C. Take the average value of 5 measurements.

[0135] (Y) In the test method (X), step (ii) is not performed to determine the peel strength.

[0136] The composition used in this embodiment is preferably a composition for temporary fixation. Hereinafter, a composition for temporary fixation will be described as an example, but its application is not limited to temporary fixation. The composition for temporary fixation in this embodiment may contain the composition of this embodiment, or it may consist solely of the composition of this embodiment.

[0137] Before describing the temporary fixation composition of this embodiment, the method of using the temporary fixation composition will be described first. Figure 1 An example of a flowchart of the wafer manufacturing method of this embodiment is shown, with the wafer's thickness direction as the plane.

[0138] First of all, Figure 1 In step S0, the temporary fixing composition 10 is applied to one side of the wafer W by spin coating or similar methods, and the wafer W is bonded to the support member 20 via the temporary fixing composition 10. Then, in step S1, the temporary fixing composition 10 is irradiated with ultraviolet light or similar light via the support member 20. In step S1, by irradiating the temporary fixing composition 10 with light, the photopolymerization initiator B in the temporary fixing composition 10 initiates a polymerization reaction of the polymerizable compound A, forming a photocured temporary fixing layer 11. Thus, the wafer W and the support member 20 are bonded via the temporary fixing layer 11. The support member 20 is not particularly limited; for example, a light-transmitting substrate such as glass can be used. Furthermore, the side of the wafer W coated with the temporary fixing composition 10 can be the element forming side.

[0139] Here, on the element forming surface of the wafer W, the semiconductor material surface such as silicon, which serves as the wafer substrate, can be exposed. In addition, the electrode material surface such as aluminum and the insulating material surface such as polyimide can also be exposed.

[0140] It should be noted that, as described above, in this specification, "temporary fixing composition" refers to a composition used to temporarily fix the wafer W onto the support member 20. Furthermore, in this specification, the cured layer obtained by irradiating the temporary fixing composition with light is referred to as a "temporary fixing layer".

[0141] Next, in step S2, the desired processing technology is performed on the wafer W, which is reinforced by the bonding support member 20. Figure 1 The example shows a process of heat treatment such as annealing for wafer W, but in addition, a grinder can be used to grind the back side of wafer W to make wafer W thinner.

[0142] Then, in step S3, the temporary fixing layer 11 is irradiated with a laser via the support member 20. In step S3, by irradiating the temporary fixing layer 11 with a laser, the polymer of the polymeric compound in the temporary fixing layer 11 is at least partially decomposed, and the bonding force between the temporary fixing layer 11 and the support member 20 is reduced. Therefore, in step S4, the support member 20 can be peeled off from the temporary fixing layer 11.

[0143] Finally, in step S5, the adhesive tape 30 is applied to the temporary fixing layer 11 after laser irradiation and peeled off in the direction of the arrow, thereby peeling the temporary fixing layer 11 off the wafer W. At this time, according to the processing technology described in step S2, the peel strength of the temporary fixing layer 11 relative to the device forming surface of the wafer W may change, and cured residue may occur due to the influence of the processing technology. Therefore, it is conceivable that a certain composition for temporary fixing is difficult to apply to a wide range of processing technologies.

[0144] In this embodiment, in the peel strength test (using polyimide as the test substrate) of steps (i) to (iv) corresponding to steps S0 to S5 above, the peel strength X after heat treatment step (ii) is specified. PI Peel strength Y compared to the case without heat treatment process (ii) PI And their ratio, can form a temporary fixing layer that is not easily affected by the processing technology and will not remain. It should be noted that the details of the peel strength test will be described later. Steps S0 and S1 correspond to process (i), step S2 corresponds to process (ii), steps S3 and S4 correspond to process (iii), and step S5 corresponds to process (iv).

[0145] The temporary fixation composition of this embodiment will be described in detail below.

[0146] 1.1. Peel strength

[0147] In the peel strength test, the peel strength X is obtained by the determination method (X) of step (ii) of heating at 175°C for 30 minutes. PI The peel strength is below 0.50 N / mm, preferably 0.01–0.50 N / mm, 0.02–0.40 N / mm, 0.03–0.30 N / mm, or 0.04–0.20 N / mm. PI When the strength is below 0.50 N / mm, it tends to be less prone to leaving cured residue due to processing conditions. Furthermore, the peel strength X... PI When the strength is above 0.01 N / mm, the wafer W is less likely to peel off from the support member due to the reduced adhesion of the temporary fixing layer during processing such as heat treatment or back-side grinding.

[0148] In the peel strength test, the peel strength Y is obtained by the method (Y) without the step (ii) of heating at 175°C for 30 minutes. PI The peel strength is 0.10 N / mm or higher, preferably 0.10–0.70 N / mm, 0.11–0.60 N / mm, 0.12–0.55 N / mm, or 0.13–0.50 N / mm. Peel strength Y PI When the strength is 0.10 N / mm or higher, it tends to reduce the likelihood of wafer W peeling from the support member due to decreased adhesion of the temporary fixing layer during processing such as back-side grinding. Furthermore, the peel strength Y... PI When the value is below 0.70 N / mm, it tends to be less likely to produce solidified residue.

[0149] The above ratio X PI / Y PI The value is below 1.5, preferably 0.10–1.5, 0.20–1.3, 0.23–1.2, 0.25–1.1, or 0.30–1.0. Compared to X PI / Y PI When the value is below 1.5, it tends to be less prone to producing solidified residues due to processing techniques. Furthermore, compared to X... PI / Y PI Within the aforementioned range, during processing such as heat treatment or back-side grinding, it is less likely that the wafer W will peel off from the support member due to a decrease in the adhesion of the temporary fixing layer.

[0150] To achieve peel strength X PI Peel strength Y PI and X PI / Y PIWithin the aforementioned range, there are no particular limitations. For example, methods such as adjusting the proportion of hydrophobic components with hydrocarbon chains having 3 or more carbon atoms in the composition for temporary fixation, adjusting the proportion of hydrophilic components with polar groups, or adjusting the proportion of components with aromatic rings that can improve laser light absorption and thus improve laser irradiation decomposition efficiency can be listed.

[0151] Specifically, from the perspective of reducing the adhesion of highly polar polyimide after heating, the peel strength X can be reduced by increasing the number of polymerizable compounds with hydrocarbon chains having more than 3 carbon atoms. PI In addition, the peel strength X can also be adjusted by changing the content of the photopolymerization initiator and the polymerizable compound, or by using a multifunctional polymerizable compound. PI and peel strength Y PI Furthermore, from the perspective of reducing adhesive strength after laser irradiation, the peel strength X can be reduced by increasing the amount of polymerizable compounds with aromatic rings. PI and peel strength Y PI Furthermore, compared to X PI / Y PI This can be used as a method to adjust the peel strength X. PI and peel strength Y PI Adjustments will be made based on the results.

[0152] Furthermore, the above description uses polyimide as an example of an insulating part as the test substrate, but aluminum as an example of an electrode part or silicon as an example of a semiconductor substrate can also be used as the test substrate, and the peel strength X after process (ii) of heating at 175°C for 30 minutes can be specified by peel strength test. Al X Si Peel strength Y compared to the condition without process (ii) Al Y Si Therefore, for patterned wafers with multiple component surfaces such as aluminum or silicon in addition to polyimide, it is less likely to generate cured residue due to processing effects. The following is a detailed explanation of these peel strengths.

[0153] In the peel strength test, the peel strength X is obtained by the determination method (X) of step (ii) of heating at 175°C for 30 minutes. Al Preferably, the peel strength is below 0.60 N / mm, 0.10–0.60 N / mm, 0.15–0.50 N / mm, or 0.20–0.40 N / mm. Al When the strength is below 0.60 N / mm, it tends to be less prone to curing residue caused by processing techniques. Furthermore, the peel strength X... AlWhen the strength is above 0.10 N / mm, the wafer W is less likely to peel off from the support member due to the reduced adhesion of the temporary fixing layer during processing such as heat treatment or back-side grinding.

[0154] In the peel strength test, the peel strength Y is obtained by the method (Y) without the step (ii) of heating at 175°C for 30 minutes. Al Preferably, the peel strength is 0.10 N / mm or higher, 0.10–0.60 N / mm, 0.12–0.45 N / mm, or 0.15–0.30 N / mm. Peel strength Y Al When the strength is 0.10 N / mm or higher, it tends to reduce the likelihood of wafer W peeling from the support member due to decreased adhesion of the temporary fixing layer during processing such as back-side grinding. Furthermore, the peel strength Y... Al When the strength is below 0.60 N / mm, it tends to be less likely to produce solidified residue.

[0155] The above ratio X Al / Y Al Preferably, the value is below 2.0, 1.0–2.0, 1.1–1.9, 1.2–1.8, or 1.3–1.7. Compared to X Al / Y Al When the value is below 2.0, it tends to be less prone to producing solidified residues due to processing techniques. Furthermore, compared to X... Al / Y Al Within the aforementioned range, during processing such as heat treatment or back-side grinding, it is less likely that the wafer W will peel off from the support member due to a decrease in the adhesion of the temporary fixing layer.

[0156] To achieve peel strength X Al Peel strength Y Al and X Al / Y Al Within the aforementioned range, there are no particular limitations. For example, methods such as adjusting the proportion of hydrophobic components with hydrocarbon chains having 3 or more carbon atoms in the composition for temporary fixation, adjusting the proportion of hydrophilic components with polar groups, or adjusting the proportion of components with aromatic rings that can improve the efficiency of laser irradiation decomposition can be listed.

[0157] Specifically, the peel strength X can be adjusted by increasing or decreasing the number of polymerizable compounds with hydrocarbon chains having three or more carbon atoms. Al In addition, the peel strength X can also be adjusted by changing the content of the photopolymerization initiator and the polymerizable compound, or by using a multifunctional polymerizable compound. Al and peel strength Y Al Furthermore, from the perspective of reducing adhesive strength after laser irradiation, the peel strength X can be reduced by increasing the amount of polymerizable compounds with aromatic rings.Al and peel strength Y Al Furthermore, compared to X Al / Y Al This can be used as a method to adjust the peel strength X. Al and peel strength Y Al Adjustments will be made based on the results.

[0158] In the peel strength test, the peel strength X is obtained by the determination method (X) of step (ii) of heating at 175°C for 30 minutes. Si Preferably, the strength is below 0.50 N / mm, 0.05–0.50 N / mm, 0.10–0.40 N / mm, or 0.15–0.30 N / mm. Peel strength X Si When the strength is below 0.50 N / mm, it tends to be less prone to leaving cured residue due to processing conditions. Furthermore, the peel strength X... Si When the strength is above 0.05 N / mm, the wafer W is less likely to peel off from the support member due to the reduced adhesion of the temporary fixing layer during processing such as heat treatment or back-side grinding.

[0159] In the peel strength test, the peel strength Y is obtained by the method (Y) without the step (ii) of heating at 175°C for 30 minutes. Si Preferably, the peel strength is 0.10 N / mm or higher, 0.10–0.60 N / mm, 0.12–0.45 N / mm, or 0.15–0.30 N / mm. Peel strength Y Si When the strength is 0.10 N / mm or higher, it tends to reduce the likelihood of wafer W peeling from the support member due to decreased adhesion of the temporary fixing layer during processing such as back-side grinding. Furthermore, the peel strength Y... Si When the strength is below 0.60 N / mm, it tends to be less likely to produce solidified residue.

[0160] The above ratio X Si / Y Si Preferably, the value is below 1.6, 0.2–1.6, 0.3–1.2, 0.5–1.1, or 0.6–1.0. Compared to X Si / Y Si When the value is below 1.6, it tends to be less prone to producing solidified residues due to processing techniques. Furthermore, compared to X... Si / Y Si Within the aforementioned range, during processing such as heat treatment or back-side grinding, it is less likely that the wafer W will peel off from the support member due to a decrease in the adhesion of the temporary fixing layer.

[0161] To achieve peel strength X Si Peel strength Y Si and XSi / Y Si Within the aforementioned range, there are no particular limitations. For example, methods such as adjusting the proportion of hydrophobic components with hydrocarbon chains having 3 or more carbon atoms in the composition for temporary fixation, adjusting the proportion of hydrophilic components with polar groups, or adjusting the proportion of components with aromatic rings that can improve the efficiency of laser irradiation decomposition can be listed.

[0162] Specifically, the peel strength X can be adjusted by increasing or decreasing the number of polymerizable compounds with hydrocarbon chains having three or more carbon atoms. Si In addition, the peel strength X can also be adjusted by changing the content of the photopolymerization initiator and the polymerizable compound, or by using a multifunctional polymerizable compound. Si and peel strength Y Si Furthermore, from the perspective of reducing adhesive strength after laser irradiation, the peel strength X can be reduced by increasing the amount of polymerizable compounds with aromatic rings. Si and peel strength Y Si Furthermore, compared to X Si / Y Si This can be used as a method to adjust the peel strength X. Si and peel strength Y Si Adjustments will be made based on the results.

[0163] Furthermore, when the wafer W is a patterned wafer with insulating and electrode portions, from the viewpoint of ensuring that the degree of cured residue is not different among the insulating portion, electrode portion, and semiconductor substrate, the peel strength X can also be specified. PI X Al X Si With peel strength Y PI Y Al Y Si The ratio is such that, for patterned wafers with both polyimide and aluminum component surfaces, it is less likely to produce cured residues due to processing influences.

[0164] From this perspective, compared to X PI / X Al Preferably, the values ​​are 0.10–0.50, 0.11–0.40, 0.12–0.35, 0.13–0.30, and 0.15–0.25. This is achieved by making the ratio X... PI / X Al Within the above range, the removal rate of the composition for temporary fixation tends to be superior.

[0165] In addition, compared to X PI / X Si Preferably, the values ​​are 0.10–0.50, 0.12–0.40, 0.15–0.38, 0.16–0.35, and 0.18–0.30. This is achieved by adjusting the ratio X...PI / X Si Within the above range, the removal rate of the composition for temporary fixation tends to be superior.

[0166] As described above, in the peel strength test of this embodiment, polyimide, aluminum, or silicon is used as the test substrate to determine the peel strength. However, this peel strength should not be limited to a value specific to polyimide, aluminum, or silicon. That is, the peel strength of polyimide X PI Y PI The peel strength X and Y of aluminum have technical significance as reference values ​​for insulating parts made of materials similar to polyimide. Al Y Al This has technical significance as a reference value for the peel strength X and Y of electrode portions made of materials similar to aluminum. Furthermore, the peel strength X of silicon... Si Y Si It has technical significance as a reference value for the peel strength X and Y of a semiconductor substrate made of a silicon-like material.

[0167] Next, the peel strength test will be described in detail. In this specification, the peel strength after heat treatment is measured using the above-described test method (X). Test method (X) corresponds to the manufacturing conditions when the wafer is temporarily fixed to the support member using the temporary fixing composition of this embodiment and the wafer is heat treated.

[0168] In step (i), a temporary fixing composition is coated onto a test substrate with a thickness of 70 μm. After the glass plate is bonded together, the temporary fixing composition is photocured to form a coating film. Step (i) corresponds to the bonding step S0 and the curing step S1 in the wafer manufacturing method described later.

[0169] In step (i), the method of coating the temporary fixing composition is not particularly limited, as long as it can be coated to a thickness of 70 μm. Examples include spin coating, screen printing, and various coating machines, among which spin coating is preferred. Spin coating refers to a method in which the temporary fixing composition, as a liquid composition, is dropped onto a wafer or support member, and the composition is coated onto the surface of the substrate by rotating the wafer or support member at a specified rotation speed.

[0170] In step (i), when the temporary fixing composition is photocured, it can be irradiated with ultraviolet light, for example. The wavelength of the ultraviolet light can be, for example, in the range of 350 to 405 nm. The energy of the ultraviolet light is preferably, for example, 1 to 20,000 mJ / cm² in the range of 350 to 405 nm. 2 The preferred value is 1000–10000 mJ / cm². 2The ultraviolet light is irradiated in the manner described in the examples. The resulting coating is equivalent to a temporary fixing layer formed by the temporary fixing composition of this embodiment.

[0171] In step (ii), the test substrate with the coating film is heated at 175°C for 30 minutes. Step (ii) corresponds to the heat treatment step S2 in the wafer manufacturing method described later.

[0172] In step (iii), the coating is irradiated with an energy density of 920 mJ / cm² at a wavelength of 355 nm and a frequency of 40 kHz. 2 After laser treatment, the glass plate is peeled off. Step (iii) corresponds to the laser irradiation step S3 and the peeling step S4 in the wafer manufacturing method described later.

[0173] In step (iii), the irradiated laser can be used under the conditions of a spot diameter of 150 μm and a pulse energy of 165 μJ, or it can be used under the conditions described in the examples.

[0174] In step (iv), a release tape is applied to the coating. The peel strength when the coating is peeled from the test substrate is measured under the following conditions: peel direction 180 degrees, peel width 20 mm, peel speed 120 mm / min, and temperature 25°C. The average value of 5 measurements is taken as the measured value. Step (iv) corresponds to the removal step S5 in the wafer manufacturing method described later.

[0175] In step (iv), the peeling tape used can be cutting tape used to fix workpieces in the cutting process of semiconductor, electronic component, and optical component manufacturing, or the tape used in the examples. The peel strength measurement method in step (iv) can be performed under the conditions described in the examples.

[0176] In this specification, the peel strength without heat treatment was measured using the above-described test method (Y). Test method (Y) corresponds to the manufacturing conditions under which the wafer is temporarily fixed to the support member using the temporary fixing composition of this embodiment and the wafer is processed without heat treatment.

[0177] 1.2. Viscosity

[0178] The viscosity of the temporary fixing composition at 23°C is preferably 500–10000 mPa·s, 600–9000 mPa·s, 700–8000 mPa·s, 800–7000 mPa·s, or 1000–6000 mPa·s. When the viscosity at 23°C is within the above range, the coatability of the temporary fixing composition is further improved.

[0179] The viscosity at 23°C can be controlled by adjusting the proportions of the components in the temporary fixing composition. For example, the viscosity of the temporary fixing composition can be reduced by increasing the amount of the low-viscosity component.

[0180] The viscosity at 23°C was determined according to the method in JIS Z8803:2011, at a temperature of 23°C and a shear rate of 1 sec. -1 The viscosity is measured, for example, using an E-type viscometer (speed example: 10 rpm or 2 rpm), with a cone plate as the measuring fixture. Specifically, it can be measured using the method described in the examples.

[0181] 1.3. Composition

[0182] The composition of the temporary fixation composition in this embodiment is not particularly limited as long as it can be cured by irradiation with ultraviolet light, the temporary fixation layer formed therefrom can be decomposed by irradiation with a laser, and the peel strength condition described above is met. The temporary fixation composition may contain, for example, a polymerizable compound A and a photopolymerization initiator B. In this case, the temporary fixation composition can be cured by irradiation with ultraviolet light. When the temporary fixation composition is irradiated with ultraviolet light, the photopolymerization initiator B is activated by the ultraviolet light, initiating the polymerization of the polymerizable compound A. The polymerization of the polymerizable compound A is completed, thereby forming a temporary fixation layer. The temporary fixation composition may further contain components other than the polymerizable compound A and the photopolymerization initiator B.

[0183] 1.3.1. Polymer compound A

[0184] There are no particular limitations on the polymerizable compound A as long as it has one or more polymerizable functional groups. Examples include polymerizable compound A1 with a hydrocarbon chain having 3 or more carbon atoms, polymerizable compound A2 with an aromatic ring, polymerizable compound A3 with a hydrocarbon chain (hereinafter also referred to as "long hydrocarbon chain") and an aromatic ring having 3 or more carbon atoms, and other polymerizable compounds A4.

[0185] Preferably, polymeric compound A comprises at least one selected from polymeric compounds A1, A2, and A3, and more preferably comprises at least polymeric compounds A1 and A2. By adjusting the content of polymeric compounds A1 to A3, the concentration of hydrocarbon chains with 3 or more carbon atoms and the concentration of aromatic rings in the temporary fixation composition can be controlled. It should be noted that in this embodiment, polymeric compound A1 does not have an aromatic ring, polymeric compound A2 does not have a long hydrocarbon chain, and polymeric compound A4 has neither an aromatic ring nor a long hydrocarbon chain. Polymeric compounds A1 to A4 can be used independently or in combination of two or more.

[0186] In this embodiment, the polymerizable functional group is not particularly limited, and examples include groups having carbon-carbon double bonds such as vinyl, allyl, butenyl, ethynyl, acryloyl, acryloyloxy, acryloylamino, methacryloyl, methacryloyloxy, methacryloylamino, ethyleneoxy, ethyleneamino, cyclopropyl, and cyclobutyl. Among these, groups containing olefinic double bonds are preferred, and (meth)acryloyl is more preferred. That is, polymerizable compound A preferably contains (meth)acrylate.

[0187] Furthermore, the content of polymeric compound A relative to the total amount of the temporary fixation composition is preferably 50–99.9% by mass, 70–99.5% by mass, 80–99.2% by mass, 90–99.0% by mass, or 95–98.8% by mass. When the content of polymeric compound A is within the above range, it tends to be less likely to produce solidified residue.

[0188] The following is a detailed description of each polymerizable compound.

[0189] There are no particular limitations on the polymerizable compound A1, as long as it has a long hydrocarbon chain and one or more polymerizable functional groups. Examples include: monofunctional polymerizable compounds such as isostearyl methacrylate; 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate (the number of repeating units can be 1 to 10), neopentyl glycol di(meth)acrylate, C1 to C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, caprolactone modified hydroxypentaenoic acid neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethylene oxide modified hydrogenated bisphenol A di(meth)acrylate; and polymers having polymerizable functional groups comprising (meth)acrylate monomers with long hydrocarbon side chains and (meth)acrylate monomers with (meth)acryloyl groups as side chains as monomer units (hereinafter also referred to as "macromonomers"), etc. Among these, (meth)acrylates containing long hydrocarbon chains are preferred.

[0190] Examples of (meth)acrylate monomers containing long hydrocarbon chains in their side chains include propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, with butyl (meth)acrylate being the preferred choice.

[0191] Examples of (meth)acrylate monomers containing (meth)acryloyl groups in their side chains include (meth)acrylates in which (meth)acryloyl groups are attached to the side chains via suitable linking groups. The linking groups can be hydrocarbon chains with 3 to 20 or 4 to 10 carbon atoms, which may contain ether bonds and / or amide bonds.

[0192] The hydrocarbon chain of polymeric compound A1 has 3 or more carbon atoms, preferably 3 to 20, 3 to 18, or 4 to 16, or 8 to 12. Polymeric compound A1 can have hydrocarbon chains with different numbers of carbon atoms in a single molecule, but preferably includes a (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms. This (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms can be a bifunctional (meth)acrylate or a (meth)acrylate with (meth)acryloyl groups at both ends of the molecular chain. The number of carbon atoms in the hydrocarbon chain is preferably 8 to 15. The content of the (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms, and the content of polymeric compound A1 with a hydrocarbon chain having 8 or more carbon atoms, relative to 100 parts by mass of polymeric compound A, is preferably 0 to 70 parts by mass, 10 to 60 parts by mass, or 20 to 55 parts by mass.

[0193] The functional group equivalent of the hydrocarbon long chain in polymeric compound A1 is preferably 100–600 g / mol. Polymeric compound A1 preferably contains polymeric compounds with a functional group equivalent of 200 g / mol or less, 100–200 g / mol, or 110–190 g / mol. When the functional group equivalent of the hydrocarbon long chain is within the above range, it tends to be less likely to produce solidified residues. The content of polymeric compound A1 with a functional group equivalent of the hydrocarbon long chain within the above range, relative to 100 parts by mass of polymeric compound A, is preferably 3–90 parts by mass, 5–70 parts by mass, 10–60 parts by mass, or 15–50 parts by mass.

[0194] The content of polymeric compound A1 relative to 100 parts by mass of polymeric compound A is preferably 50-98 parts by mass, 55-95 parts by mass, 60-92 parts by mass, or 64-90 parts by mass. By keeping the content of polymeric compound A1 within the above range, it is less likely to produce residues of cured material.

[0195] There are no particular limitations on the polymerizable compound A2, as long as it has an aromatic ring and one or more polymerizable functional groups. Examples include: phenol-modified ethylene oxide (meth)acrylate (ethylene oxide repeating units numbered 1 to 5), 2-(2'-hydroxy-5'-(meth)acryloyloxyethylphenyl)-2H-benzotriazole, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl (meth)acrylate, and monofunctional polymerizable compounds such as 2-(2-(meth)acryloyloxy,5-methyl)phenyl-2H-benzotriazole; 9,9-bis[4-(2-hydroxyC1~C1] 20 [Alkoxy]phenyl]fluorene di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20 Alkyl)benzene, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2'-dihydroxy-4,4'-diethoxy(meth)acryloyloxybenzophenone, 1,1-bis-[2-(meth)acryloyloxy,3-(2H-benzotriazol-2-yl),5-tert-octyl]methane, and other multifunctional polymerizable compounds. Among these, (meth)acrylates containing an aromatic ring are preferred.

[0196] The aromatic ring equivalent of polymeric compound A2 is preferably 100–400 g / mol. Polymeric compound A2 preferably comprises polymeric compounds with an aromatic ring equivalent of 200 g / mol or less, 100–200 g / mol, or 110–190 g / mol. When the aromatic ring equivalent is within the above range, the laser-induced decomposition tendency tends to be further improved, and the residue of the cured product is less likely to be generated. The content of polymeric compound A2 with an aromatic ring equivalent within the above range, relative to 100 parts by mass of the total amount of polymeric compound A, is preferably 1–45 parts by mass, 2–40 parts by mass, 3–35 parts by mass, or 5–25 parts by mass.

[0197] The polymerizable compound A2 preferably includes polymerizable compound A2-1 containing groups that absorb light with wavelengths of 350–385 nm. More preferably, polymerizable compound A2-1 has an absorption peak for light with wavelengths of 350–385 nm. Although the absorption peak of aromatic rings is typically around 200 nm, when the element adjacent to the aromatic ring is a heteroelement such as P, S, or O, the conjugation length increases, and absorption of light with wavelengths of 350–385 nm begins. By including such a polymerizable compound A2-1, when laser light is irradiated onto the temporary fixing layer, the laser's decomposition ability is further improved, and residues tending towards the cured material are less likely to occur.

[0198] Examples of such polymerizable compounds A2-1 include compounds having one or more skeletons selected from benzophenone, benzotriazole, triazole, hydroxyphenyltriazine, and phenol. Phenolic skeletons are preferred, and hindered phenol skeletons are more preferred.

[0199] The content of polymeric compound A2 relative to 100 parts by mass of polymeric compound A is preferably 2 to 50 parts by mass, 5 to 45 parts by mass, 8 to 40 parts by mass, or 9 to 35 parts by mass. By keeping the content of polymeric compound A2 within the above range, the decomposition properties of the laser are further improved, and the residue of the cured product is less likely to be generated.

[0200] When polymeric compound A2 contains polymeric compound A2-1, the content of polymeric compound A2-1 relative to the total amount of polymeric compound A (100 parts by mass) is preferably 1 to 30 parts by mass, 2 to 25 parts by mass, 3 to 20 parts by mass, or 5 to 15 parts by mass. By keeping the content of polymeric compound A2-1 within the above range, the decomposition properties of the laser are further improved, and the residue of the cured product is less likely to be generated.

[0201] Polymerizable compound A3 is not particularly limited; examples include monofunctional polymerizable compounds such as nonylphenol ethylene oxide-modified (meth)acrylates (ethylene oxide has 1-5 repeating units); C1-C 20 Alkoxylated bisphenol A di(meth)acrylate and other multifunctional polymeric compounds.

[0202] The functional group equivalent of the hydrocarbon long chain in polymeric compound A3 is preferably 100–800 g / mol. Polymeric compound A3 preferably contains polymeric compounds with a functional group equivalent of 500 g / mol or less, 100–500 g / mol, or 200–400 g / mol. When the functional group equivalent of the hydrocarbon long chain is within the above range, it tends to be less likely to produce solidified residues. The content of polymeric compound A3 with a functional group equivalent of the hydrocarbon long chain within the above range, relative to 100 parts by mass of polymeric compound A, is preferably 0–48 parts by mass, 0–40 parts by mass, 0–10 parts by mass, or 0–5 parts by mass.

[0203] The aromatic ring equivalent of polymeric compound A3 is preferably 100–500 g / mol. Polymeric compound A3 preferably comprises polymeric compounds with an aromatic ring equivalent of 500 g / mol or less, 100–500 g / mol, or 200–400 g / mol. When the aromatic ring equivalent is within the above range, the decomposition properties of the laser are further improved, and the residue of the cured product is less likely to be generated. The content of polymeric compound A3 with an aromatic ring equivalent within the above range, relative to 100 parts by mass of the total amount of polymeric compound A, is preferably 0–40 parts by mass, 0–10 parts by mass, or 0–5 parts by mass.

[0204] The hydrocarbon chain of polymeric compound A3 has 3 or more carbon atoms, preferably 3 to 20, 3 to 18, or 4 to 16, or 8 to 12. Polymeric compound A3 can have hydrocarbon chains with different numbers of carbon atoms in a single molecule, but it can also contain (meth)acrylates with hydrocarbon chains having 8 or more carbon atoms. The (meth)acrylate with hydrocarbon chains having 8 or more carbon atoms can be a monofunctional (meth)acrylate. The number of carbon atoms in the hydrocarbon chain is preferably 8 to 15.

[0205] The content of polymeric compound A3 relative to 100 parts by mass of the total amount of polymeric compound A is preferably 0 parts by mass or more, 3 parts by mass or more, 5 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more. Furthermore, the content of polymeric compound A3 relative to 100 parts by mass of the total amount of polymeric compound A is preferably 40 parts by mass or less, 35 parts by mass or less, 30 parts by mass or less, or 10 parts by mass or less. The content of polymeric compound A3 can also be 0 parts by mass. By keeping the content of polymeric compound A3 within the above range, the decomposition properties of the laser are further improved, and the residue of the cured product is less likely to occur.

[0206] The polymerizable compound A4 is not particularly limited; examples include 1,3-di(meth)acryloyloxyadamantane, tricyclic C 10 ~C 20 Alkane-diethanol di(meth)acrylate, bicyclic C5-C 20 Multifunctional polymeric compounds such as di(meth)acrylate.

[0207] The content of polymeric compound A4 relative to the total amount of polymeric compound A is preferably 10 parts by mass or less, 0 to 5 parts by mass, or 0 to 3 parts by mass. Alternatively, polymeric compound A4 may not be present.

[0208] Furthermore, polymeric compound A preferably comprises a polyfunctional polymeric compound having two or more polymeric functional groups per molecule, and more preferably comprises a monofunctional polymeric compound having one polymeric functional group per molecule and a polyfunctional polymeric compound having two or more polymeric functional groups per molecule. By containing a polyfunctional polymeric compound, the adhesive strength of the temporary fixing layer formed by curing the temporary fixing composition tends to be improved. In addition, by containing both polyfunctional and monofunctional polymeric compounds, it is easier to control the aforementioned hydrocarbon chain concentration and aromatic ring concentration of the temporary fixing composition.

[0209] The polyfunctional polymerizable compound is preferably a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate can be a monomer, a macromonomer, or a mixture thereof, but preferably contains a macromonomer.

[0210] Polyfunctional (meth)acrylates can be manufactured according to the methods described in, for example, Japanese Patent Application Publication No. 61-207478, Japanese Patent Application Publication No. 61-31330, Japanese Patent Application Publication No. 10-278207, Japanese Patent Application Publication No. 9-40741, and Japanese Patent Application Publication No. 8-357621.

[0211] In this embodiment, the weight-average molecular weight of the polyfunctional (meth)acrylate, which is the macromonomer, is preferably 5,000 to 500,000, 10,000 to 300,000, 30,000 to 200,000, or 50,000 to 100,000. When the weight-average molecular weight is within the above range, it is preferable to control the viscosity of the temporary fixing composition and the crosslinking density of the cured product within the preferred range. The polyfunctional polymerizable compound may be contained as polymerizable compound A1.

[0212] The weight-average molecular weight in this specification is a converted value of standard polystyrene determined by gel permeation chromatography (GPC). Specifically, the weight-average molecular weight was obtained by using tetrahydrofuran as a solvent and a GPC system (Tosoh Corporation SC-8010) to create a calibration curve using commercially available standard polystyrene under the following conditions.

[0213] Flow rate: 1.0 ml / min

[0214] Set temperature: 40℃

[0215] The chromatographic column consisted of one 6.0mm ID×4.0cm "TSKguardcolumn MP(×L)" column manufactured by Tosoh, and two 7.8mm ID×30.0cm "TSK-GELMULTIPOREHXL-M" columns manufactured by Tosoh (16,000 theoretical plates), for a total of three columns (overall theoretical plate count 32,000).

[0216] Injection volume: 100 μl (sample concentration 1 mg / ml)

[0217] Liquid delivery pressure: 39 kg / cm 2

[0218] Detector: RI detector

[0219] Polymer compound A preferably comprises both monofunctional and polyfunctional polymeric compounds. In this case, the content of the monofunctional polymeric compound relative to 100 parts by mass of the total polyfunctional polymeric compound is preferably 0.01 to 80 parts by mass, 0.50 to 70 parts by mass, 1.0 to 68 parts by mass, or 3.0 to 67 parts by mass. By keeping the content of the monofunctional polymeric compound within the above range, it is less likely to produce residues of cured material, and it is easier to adjust the viscosity and heat resistance.

[0220] 1.3.2. Photopolymerization initiator B

[0221] Photopolymerization initiator B is preferably a photoradical polymerization initiator, and more preferably a compound that breaks down into two or more free radicals by irradiation with ultraviolet or visible light.

[0222] Photopolymerization initiator B can be selected by measuring absorbance to identify compounds with suitable absorption characteristics. Specifically, photopolymerization initiator B can be selected from one or more compounds that meet at least one of the following conditions: when dissolved at a concentration of 0.1% by mass in a solvent (e.g., acetonitrile or toluene) that does not have maximum absorption in the 300–500 nm wavelength region, it has an absorbance of 0.5 or more at a wavelength of 365 nm, an absorbance of 0.5 or more at a wavelength of 385 nm, and an absorbance of 0.5 or more at a wavelength of 405 nm.

[0223] As the photopolymerization initiator B, it is preferably selected from one or more of acylphosphine oxide compounds, diaceticolide compounds, and α-aminoalkylphenyl ketone compounds due to its excellent reaction rate and heat resistance after curing. These compounds tend to have absorption wavelengths in the range of about 440 nm or less, and are preferred because they have low absorbance at the wavelength of light used in the process of irradiating the temporary fixing layer with a laser. That is, the above-mentioned photopolymerization initiator B is a photopolymerization initiator capable of initiating free radical polymerization under longer wavelengths of light. Therefore, the difference between the wavelength of the irradiation light used to cure the temporary fixing composition and the wavelength of the laser used to decompose the temporary fixing layer can be increased. Furthermore, oxime ester compounds can also be selected as the photopolymerization initiator B.

[0224] Examples of acylphosphine oxide compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyl diphenylphosphine oxide. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.

[0225] Examples of titanium-based compounds include bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrolo-1-yl)-phenyl)titanium.

[0226] Examples of α-aminoalkylphenyl ketone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one and 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholino-4-ylphenyl)-butane-1-one.

[0227] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyl oxime and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime). Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime) is preferred.

[0228] From the viewpoint of exhibiting high absorption in the 365–405 nm wavelength region, the preferred photopolymerization initiator B is 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime), 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyl oxime, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and 2,4,6-trimethylbenzoyl diphenylphosphine oxide, with bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide being more preferred.

[0229] In addition, bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl)titanium, which exhibits absorption in the longer wavelength range of 400–500 nm, is also preferred.

[0230] The content of photopolymerization initiator B relative to 100 parts by mass of the total amount of polymerizable compound A is preferably 0.01 to 10 parts by mass, 0.01 to 5.0 parts by mass, 0.1 to 3.0 parts by mass, or 0.5 to 1.5 parts by mass. When the content of photopolymerization initiator B is within the above range, it tends to further improve the adhesion of the temporary fixing layer formed using the temporary fixing composition.

[0231] 1.3.3. Other ingredients

[0232] The temporary fixation composition may contain components other than polymerizable compound A and photopolymerization initiator B. Examples of such components include compounds that are not polymerizable compounds, have aromatic rings, or have hydrocarbon chains with three or more carbon atoms.

[0233] 2. Uses

[0234] The temporary fixing composition of this embodiment can preferably be used in a wafer manufacturing process to temporarily fix a wafer, particularly a patterned wafer, to a support member. The temporary fixing composition is preferably applied to the wafer surface to temporarily fix the wafer to the support member for processing the back side of the wafer. Since the temporary fixing composition of this embodiment is less likely to produce cured residue even when heat-treating patterned wafers, it can preferably be used in manufacturing methods that include a process of heat-treating patterned wafers.

[0235] 3. Chip manufacturing methods

[0236] like Figure 1 As shown, the wafer manufacturing method of this embodiment includes: a step of bonding the wafer to a support member via the temporary fixing composition of this embodiment (hereinafter referred to as bonding step S0); a step of curing the temporary fixing composition by irradiating it with ultraviolet light to form a temporary fixing layer, and bonding the wafer to the support member via the temporary fixing layer (hereinafter referred to as curing step S1); a step of heat-treating the wafer (hereinafter referred to as heat treatment step S2); a step of irradiating the temporary fixing layer with a laser (hereinafter referred to as laser irradiation step S3); and a step of peeling the support member from the wafer at the interface of the temporary fixing layer (hereinafter referred to as peeling step S4).

[0237] In the bonding process S0, the wafer is bonded to the support member. The wafer is the substrate to be processed, such as a silicon substrate. The wafer is preferably a patterned wafer, more preferably a wafer with polyimide and aluminum patterns formed on it. Furthermore, the support member is preferably a support member that can transmit at least ultraviolet light, such as a glass plate.

[0238] The bonding method in bonding process S0 is not particularly limited, but it is preferable to apply the temporary fixing composition of this embodiment to one side of the wafer or support member and then bond another substrate.

[0239] As a coating method for the composition used for temporary fixation, known coating methods such as spin coating, screen printing, and various coating machines can be used, but spin coating is preferred.

[0240] In the curing step S1, the temporary fixing composition is cured by irradiating it with ultraviolet light, thus bonding the wafer to the support member. By using a transparent substrate that transmits at least ultraviolet light as at least one of the wafer and the support member, the temporary fixing composition can be easily irradiated with ultraviolet light. When an ultraviolet-transmitting substrate is used as the support member, ultraviolet light can be irradiated from the support member side. Examples of transparent substrates include inorganic substrates such as crystal, glass, quartz, calcium fluoride, and magnesium fluoride, as well as organic substrates such as plastics, but inorganic substrates are preferred.

[0241] The wavelength of the ultraviolet light can be appropriately selected according to the type of photopolymerization initiator B, for example, within the range of 350–405 nm. Preferably, the energy of the ultraviolet light within the 350–405 nm range is, for example, 1–20000 mJ / cm². 2 The preferred value is 1000–10000 mJ / cm². 2 Irradiation is performed in this manner.

[0242] In heat treatment step S2, the wafer is heat-treated. Heat treatment refers to processing at high temperatures above 170°C, with the temperature range being 170–300°C. In heat treatment step S2, the wafer can be heated and subjected to various processing procedures. Examples of such processing include forming an insulating film, forming circuits, and ion implantation on the surface of the wafer opposite to the surface to which the support member is attached.

[0243] Laser irradiation step S3 is a step in which a laser is irradiated onto the temporary fixing layer, which is a cured temporary fixing composition, to decompose the temporary fixing layer. The wavelength of the laser is preferably 350 to 385 nm. The laser can irradiate from the wafer side or the support member side, but irradiation from the support member side is preferred. As mentioned above, when the temporary fixing composition contains an aromatic ring bonded to heteroatoms, it tends to absorb laser energy more easily in laser irradiation step S3.

[0244] In the stripping process S4, the support member is peeled from the wafer at the interface of the temporary fixing layer. In the laser irradiation process, the temporary fixing layer decomposes, generating gas from the decomposition components. The adhesion between the temporary fixing layer and the wafer or support member decreases, thereby allowing the wafer to be peeled from the support member.

[0245] The wafer manufacturing method of this embodiment preferably includes a step (hereinafter referred to as removal step S5) to remove the temporary fixing layer after laser irradiation from the wafer peeled off from the self-supporting member. By performing the removal step S5, the temporary fixing layer can be sufficiently removed even if it remains on the wafer.

[0246] The removal process S5 is not particularly limited, as long as it can remove the temporary fixing layer remaining on the wafer. For example, a method can be used where adhesive tape is applied to a wafer with a residual temporary fixing layer, and then the adhesive tape is peeled off the wafer. In this method, the remaining temporary fixing layer is attached to the adhesive tape, so the temporary fixing layer can be removed along with the adhesive tape when peeling it off the wafer. For example, cutting tape used in the dicing process of semiconductor, electronic component, and optical component manufacturing can be used to fix workpieces.

[0247] In the above-described wafer manufacturing method, the processing step S2, in which the wafer W, reinforced by bonding with the support member 20, undergoes the desired processing, is described as "heat treatment step S2." However, the processing is not limited to heat treatment; it may also include processing the surface of the wafer opposite to the surface to which the support member is attached, under non-heating conditions before or after heat treatment, particularly before heat treatment. Examples of such processing include thinning by grinding / polishing. As described above, the peel strength of the temporary fixing composition of this embodiment, measured by the measurement method (Y), is within a specified range, thus suppressing the wafer from peeling off from the support member in the above-described processing step.

[0248] Provided there is no contradiction, the temporary fixation composition of the first embodiment can possess the characteristics of the temporary fixation composition of the second embodiment.

[0249] [Second Implementation]

[0250] 1. Compositions and compositions for temporary fixation

[0251] The composition of this embodiment contains polymerizable compound A and photopolymerization initiator B, and the concentration of hydrocarbon chains with 3 or more carbon atoms (hereinafter also referred to as "long hydrocarbon chains") is 2.80 mmol / g or more, and the concentration of aromatic rings is 0.60 mmol / g or more.

[0252] The composition used in this embodiment is preferably a composition for temporary fixation. Hereinafter, a composition for temporary fixation will be described as an example, but its application is not limited to temporary fixation. The composition for temporary fixation in this embodiment may contain the composition of this embodiment, or it may consist solely of the composition of this embodiment.

[0253] Before describing the temporary fixation composition of this embodiment, the method of using the temporary fixation composition will be explained first. Figure 2 An example of a flowchart of the wafer manufacturing method of this embodiment is shown, with the wafer's thickness direction as the plane.

[0254] First of all, Figure 2In step S1, the temporary fixing composition 10 is coated onto one side of the wafer W by spin coating or similar methods, and the wafer W is bonded to the support member 20 via the temporary fixing composition 10. The temporary fixing composition 10 is then irradiated with ultraviolet light or similar light via the support member 20. In step S1, by irradiating the temporary fixing composition 10 with light, the photopolymerization initiator B in the temporary fixing composition 10 initiates a polymerization reaction of the polymerizable compound A, forming a photocured temporary fixing layer 11. Thus, the wafer W and the support member 20 are bonded via the temporary fixing layer 11. The support member 20 is not particularly limited; for example, a light-transmitting substrate such as glass can be used. Furthermore, the side of the wafer W coated with the temporary fixing composition 10 can be the element forming side.

[0255] It should be noted that, as described above, in this specification, "temporary fixing composition" refers to a composition used to temporarily fix the wafer W onto the support member 20. Furthermore, in this specification, the cured layer obtained by irradiating the temporary fixing composition with light is referred to as a "temporary fixing layer".

[0256] Next, in step S2, the other side of the wafer W is ground by the grinding machine G, making the wafer W thinner. Other processes such as annealing may also be performed before or after step S2.

[0257] Then, in step S3, the temporary fixation layer 11 is irradiated with laser light via the support member 20. In step S3, by irradiating the temporary fixation layer 11 with laser light, the polymer of the polymeric compound A in the temporary fixation layer 11 is at least partially decomposed, and the bonding force between the temporary fixation layer 11 and the support member 20 decreases. Therefore, in step S4, the support member 20 can be peeled off from the temporary fixation layer 11. At this time, since the concentration of aromatic rings in the temporary fixation composition of this embodiment is above a predetermined value, the laser absorption is increased, thus further improving the peelability of the temporary fixation layer 11 from the support member 20 by laser irradiation.

[0258] Finally, in step S5, the adhesive tape 30 is applied to the temporary fixing layer 11 after laser irradiation and peeled off in the direction of the arrow, thereby removing the temporary fixing layer 11 from the wafer W. It should be noted that the wafer W is made of semiconductor materials such as Si, but its surface is oxidized to Si-O, etc., and is generally in a state where hydrogen bonding and other interactions are likely to occur. Therefore, since the concentration of hydrocarbon chains with 3 or more carbon atoms in the temporary fixing composition of this embodiment is at or above a predetermined value, hydrogen bonding and other interactions between the temporary fixing layer 11 and the surface of the wafer W are reduced, preventing the temporary fixing layer 11 from remaining on the surface of the wafer W.

[0259] As described above, the temporary fixation composition of this embodiment can form a temporary fixation layer with excellent laser ablation properties and is not easily left on the wafer. Hereinafter, the temporary fixation composition of this embodiment will be described in detail.

[0260] 1.1. Hydrocarbon chain concentration

[0261] The concentration of hydrocarbon chains with 3 or more carbon atoms is 2.80 mmol / g or higher, preferably 2.90–50.0 mmol / g, 3.00–30.0 mmol / g, 3.10–20.0 mmol / g, 3.20–10.0 mmol / g, 3.30–6.00 mmol / g, or 3.40–5.20 mmol / g. When the concentration of long hydrocarbon chains is 2.80 mmol / g or higher, it is less likely to produce solidified residue. Furthermore, when the concentration of long hydrocarbon chains is 50.0 mmol / g or lower, it tends to further improve the adhesion of the wafer, i.e., the peel strength.

[0262] In this specification, "hydrocarbon chain" refers to a straight or branched saturated or unsaturated hydrocarbon group. Furthermore, the number of carbon atoms in the long hydrocarbon chain is 3 or more, preferably 3 to 20, 3 to 18, or 4 to 16, or 8 to 12.

[0263] Furthermore, the long hydrocarbon chain can be a monovalent group located at the end of the molecule, or a divalent or higher group located within the molecule. The valence of the long hydrocarbon chain is preferably 1 to 4, 1 to 3, or 1 to 2. As a long hydrocarbon chain, a saturated hydrocarbon chain is preferred, but a straight-chain hydrocarbon chain is also preferred. Particularly preferred is that the hydrocarbon chain is a straight-chain saturated hydrocarbon group with a valence of 1 to 2.

[0264] The aforementioned long hydrocarbon chains are not particularly limited, and examples include: monovalent saturated hydrocarbon groups such as propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl; monovalent unsaturated hydrocarbon groups such as vinyl, propynyl, butynyl, pentynyl, hexynyl, octyynyl, decynyl, dodecaynyl, hexadecynyl, and octadecynyl; and divalent saturated hydrocarbon groups such as propylidene, butylidene, pentylidene, hexylidene, and heptylidene, but monovalent or divalent saturated hydrocarbon groups are preferred.

[0265] The aforementioned long hydrocarbon chains can be derived from either polymerizable compound A or photopolymerizable initiator B. The concentration of hydrocarbon chains with 3 or more carbon atoms can be determined from the molecular structure and content of the components contained in the temporary fixation composition. It should be noted that known methods can be used for the identification of molecular structures, such as component separation, NMR determination, or IR determination, as well as the quantification of content.

[0266] The aforementioned long hydrocarbon chain may be included in either polymerizable compound A or photopolymerizable initiator B, but is preferably included in polymerizable compound A, but may not be included in photopolymerizable initiator B.

[0267] 1.2. Aromatic ring concentration

[0268] The concentration of aromatic rings is 0.60 mmol / g or more, preferably 0.64–5.0 mmol / g, 0.68–4.0 mmol / g, 0.70–3.0 mmol / g, 0.80–2.5 mmol / g, 0.90–2.4 mmol / g, or 1.00–2.2 mmol / g. When the concentration of aromatic rings is 0.60 mmol / g or more, the absorption of laser, especially UV laser with a UV wavelength, increases, and the laser ablation property is further improved. In particular, in the temporary fixation composition of this embodiment, in order to reduce the residue of cured material, the hydrocarbon chain concentration is specified within the above range, so the number of carbon-carbon bonds with high binding energy and stability increases. By making the concentration of aromatic rings 0.60 mmol / g or more, excellent laser ablation property can be achieved. Furthermore, when the concentration of aromatic rings is 5.0 mmol / g or less, the interaction between the temporary fixation layer 11 and the wafer W surface is reduced, and it is less likely to produce residue of cured material.

[0269] In this specification, "aromatic ring" refers to a cyclic group that exhibits aromaticity. An aromatic ring can be a hydrocarbon aromatic ring composed of carbon and hydrogen atoms, or a heteroaromatic ring containing heteroatoms other than carbon and hydrogen atoms. Heteroaromatic rings preferably contain a nitrogen atom as a heteroatom. An aromatic ring can be a monocyclic ring such as a benzene ring, a bicyclic ring such as a naphthalene ring, a tricyclic ring such as anthracene ring, or an aromatic ring containing four or more rings, but monocyclic or bicyclic rings are preferred.

[0270] The concentration of aromatic rings is calculated on a unit based on the ring exhibiting aromaticity. For example, even structures containing multiple rings, such as naphthalene or anthracene which form a conjugated system across multiple rings, are counted as one aromatic ring. On the other hand, even structures with multiple adjacent rings, such as A-BPEF-2 used in the later examples which do not form a conjugated system across multiple rings, are counted as one aromatic ring for each aromatic ring contained in that structure.

[0271] The aromatic ring can be derived from either polymerizable compound A or photopolymerizable initiator B. The concentration of the aromatic ring can be determined from the molecular structure and content of the components contained in the temporary fixation composition. It should be noted that known methods can be used for the identification of molecular structures, such as the separation of components, NMR determination or IR determination, and the quantification of content.

[0272] The aromatic ring described above may be contained in either polymerizable compound A or photopolymerizable initiator B, but is preferably contained in both polymerizable compound A and photopolymerizable initiator B.

[0273] The preferred ratio of the concentration of long hydrocarbon chains to the concentration of aromatic rings is 0.80–15, 1.0–10, 1.1–9.0, 1.2–8.0, or 1.3–7.0. When the ratio of the concentration of long hydrocarbon chains to the concentration of aromatic rings is within the above range, the laser exfoliation property is further improved, and it tends to be less likely to produce residues of cured material.

[0274] 1.3. Crosslinking density after curing

[0275] The crosslinking density of the cured product (temporary fixation layer) after irradiation with ultraviolet light for temporary fixation is preferably 0.10 mmol / cm². 3 Above, 0.10~5.0mmol / cm 3 0.20–3.0 mmol / cm 3 0.30–2.0 mmol / cm 3 0.35–1.0 mmol / cm 3 The crosslinking density of the cured material is 0.10 mmol / cm³. 3 In the above cases, the adhesion of the temporary fixing layer tends to be maintained even under high temperature conditions. Therefore, even if desired heat treatments are performed before or after step S2, wafer delamination from the support member can be suppressed during wafer backside processing under high temperature conditions. Furthermore, the crosslinking density of the cured material is 0.10 mmol / cm³. 3 At the above levels, cohesive failure is less likely to occur, and there is a tendency to further inhibit the residue of solidified material.

[0276] The crosslinking density of the cured material (temporary fixing layer) can be controlled by adjusting the type of polymeric compound A. Specifically, the crosslinking density after curing can be increased by increasing the content of polymeric compounds with lower equivalent (g / mol) of polymeric functional groups.

[0277] The crosslinking density of the cured material can be indirectly determined by measuring the storage elastic modulus of the cured material obtained by irradiating the temporary fixation composition with ultraviolet light. Specifically, it can be determined by the method described in the examples.

[0278] 1.4. Viscosity

[0279] The viscosity of the temporary fixing composition at 23°C is preferably 500–10000 mPa·s, 600–9000 mPa·s, 700–8000 mPa·s, 800–7000 mPa·s, or 1000–6000 mPa·s. When the viscosity at 23°C is within the above range, the coatability of the temporary fixing composition is further improved.

[0280] The viscosity at 23°C can be controlled by adjusting the proportions of the components in the temporary fixing composition. For example, the viscosity of the temporary fixing composition can be reduced by increasing the amount of the low-viscosity component.

[0281] The viscosity at 23°C was determined according to the method in JIS Z8803:2011, at a temperature of 23°C and a shear rate of 1 second. -1 The viscosity is measured, for example, using an E-type viscometer (speed example: 10 rpm or 2 rpm), with a cone plate as the measuring fixture. Specifically, it can be measured using the method described in the examples.

[0282] 1.5. Composition

[0283] The temporary fixation composition of this embodiment only needs to contain polymerizable compound A and photopolymerization initiator B, and may further contain other components.

[0284] 1.5.1. Polymer compound A

[0285] There are no particular limitations on the polymerizable compound A as long as it has one or more polymerizable functional groups. Examples include polymerizable compound A1 with a hydrocarbon chain having 3 or more carbon atoms, polymerizable compound A2 with an aromatic ring, polymerizable compound A3 with a hydrocarbon chain having 3 or more carbon atoms and an aromatic ring, and other polymerizable compounds A4.

[0286] The polymeric compound A preferably includes at least one selected from polymeric compounds A1, A2, and A3. By adjusting the content of polymeric compounds A1 to A3, the concentration of hydrocarbon chains with 3 or more carbon atoms and the concentration of aromatic rings in the temporary fixation composition can be controlled. In this embodiment, polymeric compound A1 does not have an aromatic ring, polymeric compound A2 does not have a long hydrocarbon chain, and polymeric compound A4 has neither an aromatic ring nor a long hydrocarbon chain. Polymeric compounds A1 to A4 can be used independently or in combination of two or more.

[0287] In this embodiment, the polymerizable functional group is not particularly limited, and examples include groups having carbon-carbon double bonds such as vinyl, allyl, butenyl, ethynyl, acryloyl, acryloyloxy, acryloylamino, methacryloyl, methacryloyloxy, methacryloylamino, ethyleneoxy, ethyleneamino, cyclopropyl, and cyclobutyl. Among these, groups containing olefinic double bonds are preferred, and (meth)acryloyl is more preferred. That is, polymerizable compound A preferably contains (meth)acrylate.

[0288] Furthermore, the content of polymeric compound A relative to the total amount of the temporary fixation composition is preferably 50–99.9% by mass, 70–99.5% by mass, 80–99.2% by mass, 90–99.0% by mass, or 95–98.8% by mass. When the content of polymeric compound A is within the above range, laser exfoliation properties are further improved, and it is less likely to produce cured residue.

[0289] The following is a detailed description of each polymerizable compound.

[0290] There are no particular limitations on the polymerizable compound A1, as long as it has a long hydrocarbon chain and one or more polymerizable functional groups. Examples include: monofunctional polymerizable compounds such as isostearyl methacrylate; 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate (the number of repeating units can be 1 to 10), neopentyl glycol di(meth)acrylate, C1 to C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, caprolactone modified hydroxypentaenoic acid neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, ethylene oxide modified hydrogenated bisphenol A di(meth)acrylate; and polymers having polymerizable functional groups comprising (meth)acrylate monomers with long hydrocarbon side chains and (meth)acrylate monomers with (meth)acryloyl groups as side chains as monomer units (hereinafter also referred to as "macromonomers"), etc. Among these, (meth)acrylates containing long hydrocarbon chains are preferred.

[0291] Examples of (meth)acrylate monomers containing long hydrocarbon chains in their side chains include propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, with butyl (meth)acrylate being the preferred choice.

[0292] As a (meth)acrylate monomer containing a (meth)acryloyl group in the side chain, examples include (meth)acrylates in which the (meth)acryloyl group is attached to the side chain via a suitable linking group. The linking group can be a hydrocarbon chain with 3 to 20 or 4 to 10 carbon atoms, and it can contain ether bonds and / or amide bonds.

[0293] The hydrocarbon chain of polymeric compound A1 has 3 or more carbon atoms, preferably 3 to 20, 3 to 18, or 4 to 16, or 8 to 12. Polymeric compound A1 can have hydrocarbon chains with different numbers of carbon atoms in a single molecule, but preferably includes a (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms. This (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms can be a bifunctional (meth)acrylate or a (meth)acrylate with (meth)acryloyl groups at both ends of the molecular chain. The number of carbon atoms in the hydrocarbon chain is preferably 8 to 15. The content of the (meth)acrylate with a hydrocarbon chain having 8 or more carbon atoms, and the content of polymeric compound A1 with a hydrocarbon chain having 8 or more carbon atoms, relative to 100 parts by mass of polymeric compound A, is preferably 0 to 70 parts by mass, 10 to 60 parts by mass, or 20 to 55 parts by mass.

[0294] The functional group equivalent of the hydrocarbon long chain in polymeric compound A1 is preferably 100–600 g / mol. Polymeric compound A1 preferably contains polymeric compounds with a functional group equivalent of 200 g / mol or less, 100–200 g / mol, or 110–190 g / mol. When the functional group equivalent of the hydrocarbon long chain is within the above range, it tends to be less likely to produce solidified residues. The content of polymeric compound A1 with a functional group equivalent of the hydrocarbon long chain within the above range, relative to 100 parts by mass of polymeric compound A, is preferably 5–70 parts by mass, 10–60 parts by mass, or 15–50 parts by mass.

[0295] The content of polymeric compound A1 relative to 100 parts by mass of polymeric compound A is preferably 50-98 parts by mass, 55-95 parts by mass, 60-92 parts by mass, or 64-90 parts by mass. By keeping the content of polymeric compound A1 within the above range, it is less likely to produce residues of cured material.

[0296] There are no particular limitations on the polymerizable compound A2, as long as it has an aromatic ring and one or more polymerizable functional groups. Examples include: phenol-modified ethylene oxide (meth)acrylate (ethylene oxide repeating units numbered 1 to 5), 2-(2'-hydroxy-5'-(meth)acryloyloxyethylphenyl)-2H-benzotriazole, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl (meth)acrylate, and monofunctional polymerizable compounds such as 2-(2-(meth)acryloyloxy,5-methyl)phenyl-2H-benzotriazole; 9,9-bis[4-(2-hydroxyC1~C1] 20 [Alkoxy]phenyl]fluorene di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C1-C 20Alkyl)benzene, 2,2-bis(4-(meth)acryloyloxydiethoxyphenyl)propane, 2,2'-dihydroxy-4,4'-diethoxy(meth)acryloyloxybenzophenone, 1,1-bis-[2-(meth)acryloyloxy,3-(2H-benzotriazol-2-yl),5-tert-octyl]methane, and other multifunctional polymerizable compounds. Among these, (meth)acrylates containing an aromatic ring are preferred.

[0297] The aromatic ring equivalent of polymerizable compound A2 is preferably 100–400 g / mol. Polymerizable compound A2 preferably comprises polymerizable compounds with an aromatic ring equivalent of 200 g / mol or less, 100–200 g / mol, or 110–190 g / mol. When the aromatic ring equivalent is within the above range, laser exfoliation properties tend to be further improved. The content of polymerizable compound A2 with an aromatic ring equivalent within the above range, relative to 100 parts by mass of the total amount of polymerizable compound A, is preferably 1–45 parts by mass, 2–40 parts by mass, or 3–35 parts by mass.

[0298] The polymerizable compound A2 preferably includes polymerizable compound A2-1 containing groups that absorb light with wavelengths of 350–385 nm. More preferably, polymerizable compound A2-1 has an absorption peak for light with wavelengths of 350–385 nm. Although the absorption peak of aromatic rings is typically around 200 nm, when the element adjacent to the aromatic ring is a heteroelement such as P, S, or O, the conjugation length increases, and absorption of light with wavelengths of 350–385 nm begins. By including such a polymerizable compound A2-1, laser light can be efficiently absorbed when irradiating the temporary fixation layer, tending to improve laser ablation performance.

[0299] Examples of such polymerizable compounds A2-1 include compounds having one or more skeletons selected from benzophenone, benzotriazole, triazole, hydroxyphenyltriazine, and phenol. Phenolic skeletons are preferred, and hindered phenol skeletons are more preferred.

[0300] The content of polymeric compound A2 relative to 100 parts by mass of polymeric compound A is preferably 2 to 50 parts by mass, 5 to 45 parts by mass, 8 to 40 parts by mass, or 9 to 35 parts by mass. By setting the content of polymeric compound A2 within the above range, the laser exfoliation properties of the temporary fixation composition can be further improved.

[0301] When polymeric compound A2 contains polymeric compound A2-1, the content of polymeric compound A2-1 relative to the total amount of polymeric compound A (100 parts by mass) is preferably 1 to 30 parts by mass, 2 to 25 parts by mass, 3 to 20 parts by mass, or 5 to 15 parts by mass. By keeping the content of polymeric compound A2-1 within the above range, the laser exfoliation properties of the temporary fixation composition can be further improved.

[0302] Polymerizable compound A3 is not particularly limited; examples include monofunctional polymerizable compounds such as nonylphenol ethylene oxide-modified (meth)acrylates (ethylene oxide has 1-5 repeating units); C1-C 20 Alkoxylated bisphenol A di(meth)acrylate and other multifunctional polymeric compounds.

[0303] The functional group equivalent of the hydrocarbon long chain in polymeric compound A3 is preferably 100–800 g / mol. Polymeric compound A3 preferably contains polymeric compounds with a functional group equivalent of 500 g / mol or less, 100–500 g / mol, or 200–400 g / mol. When the functional group equivalent of the hydrocarbon long chain is within the above range, it tends to be less likely to produce solidified residues. The content of polymeric compound A3 with a functional group equivalent of the hydrocarbon long chain within the above range, relative to 100 parts by mass of polymeric compound A, is preferably 0–48 parts by mass, 0–40 parts by mass, 0–10 parts by mass, or 0–5 parts by mass.

[0304] The aromatic ring equivalent of polymerizable compound A3 is preferably 100–500 g / mol. Polymerizable compound A3 preferably comprises polymerizable compounds with an aromatic ring equivalent of 500 g / mol or less, 100–500 g / mol, or 200–400 g / mol. When the aromatic ring equivalent is within the above range, laser exfoliation properties tend to be further improved. The content of polymerizable compound A3 with an aromatic ring equivalent within the above range, relative to 100 parts by mass of the total amount of polymerizable compound A, is preferably 0–40 parts by mass, 0–10 parts by mass, or 0–5 parts by mass.

[0305] The hydrocarbon chain of polymeric compound A3 has 3 or more carbon atoms, preferably 3 to 20, 3 to 18, or 4 to 16, or 8 to 12. Polymeric compound A3 can have hydrocarbon chains with different numbers of carbon atoms in a single molecule, but it can also contain (meth)acrylates with hydrocarbon chains having 8 or more carbon atoms. The (meth)acrylate with hydrocarbon chains having 8 or more carbon atoms can be a monofunctional (meth)acrylate. The number of carbon atoms in the hydrocarbon chain is preferably 8 to 15.

[0306] The content of polymeric compound A3 relative to 100 parts by mass of the total amount of polymeric compound A is preferably 0 parts by mass or more, 3 parts by mass or more, 5 parts by mass or more, 20 parts by mass or more, or 25 parts by mass or more. Furthermore, the content of polymeric compound A3 relative to 100 parts by mass of the total amount of polymeric compound A is preferably 40 parts by mass or less, 35 parts by mass or less, 30 parts by mass or less, or 10 parts by mass or less. The content of polymeric compound A3 may also be 0 parts by mass. By ensuring the content of polymeric compound A3 is within the above ranges, the laser exfoliation properties of the temporary fixation composition are likely to be further improved.

[0307] The polymerizable compound A4 is not particularly limited; examples include 1,3-di(meth)acryloyloxyadamantane, tricyclic C 10 ~C 20 Alkane-diethanol di(meth)acrylate, bicyclic C5-C 20 Multifunctional polymeric compounds such as di(meth)acrylate.

[0308] The content of polymeric compound A4 relative to the total amount of polymeric compound A is preferably 10 parts by mass or less, 0 to 5 parts by mass, or 0 to 3 parts by mass. Alternatively, polymeric compound A4 may not be present.

[0309] Furthermore, polymeric compound A preferably comprises a polyfunctional polymeric compound having two or more polymeric functional groups per molecule, and more preferably comprises a monofunctional polymeric compound having one polymeric functional group per molecule and a polyfunctional polymeric compound having two or more polymeric functional groups per molecule. By containing a polyfunctional polymeric compound, the adhesive strength of the temporary fixing layer formed by curing the temporary fixing composition tends to be improved. In addition, by containing both polyfunctional and monofunctional polymeric compounds, it is easier to control the aforementioned hydrocarbon chain concentration and aromatic ring concentration of the temporary fixing composition.

[0310] The polyfunctional polymerizable compound is preferably a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate can be a monomer, a macromonomer, or a mixture thereof, but preferably contains a macromonomer.

[0311] Polyfunctional (meth)acrylates can be manufactured according to the methods described in, for example, Japanese Patent Application Publication No. 61-207478, Japanese Patent Application Publication No. 61-31330, Japanese Patent Application Publication No. 10-278207, Japanese Patent Application Publication No. 9-40741, and Japanese Patent Application Publication No. 8-357621.

[0312] In this embodiment, the weight-average molecular weight of the polyfunctional (meth)acrylate, which is the macromonomer, is preferably 5,000 to 500,000, 10,000 to 300,000, 30,000 to 200,000, or 50,000 to 100,000. When the weight-average molecular weight is within the above range, it is preferable to control the viscosity of the temporary fixing composition and the crosslinking density of the cured product within the preferred range. The polyfunctional polymerizable compound may be contained as polymerizable compound A1.

[0313] The weight-average molecular weight in this specification is a converted value of standard polystyrene determined by gel permeation chromatography (GPC). Specifically, the weight-average molecular weight was obtained by using tetrahydrofuran as a solvent and a GPC system (Tosoh Corporation SC-8010) to create a calibration curve using commercially available standard polystyrene under the following conditions.

[0314] Flow rate: 1.0 ml / min

[0315] Set temperature: 40℃

[0316] The chromatographic column consisted of one 6.0mm ID×4.0cm "TSKguardcolumn MP(×L)" column manufactured by Tosoh, and two 7.8mm ID×30.0cm "TSK-GELMULTIPOREHXL-M" columns manufactured by Tosoh (16,000 theoretical plates), for a total of three columns (overall theoretical plate count 32,000).

[0317] Injection volume: 100 μl (sample concentration 1 mg / ml)

[0318] Liquid delivery pressure: 39 kg / cm 2

[0319] Detector: RI detector

[0320] Polymer compound A preferably comprises both monofunctional and polyfunctional polymeric compounds. In this case, the content of the monofunctional polymeric compound relative to 100 parts by mass of the total polyfunctional polymeric compound is preferably 0.01–80 parts by mass, 0.50–70 parts by mass, 1.0–68 parts by mass, or 3.0–67 parts by mass. By keeping the content of the monofunctional polymeric compound within the above range, laser exfoliation properties are further improved, it is less likely to produce cured residue, and viscosity and heat resistance are more easily adjusted.

[0321] 1.5.2. Photopolymerization initiator B

[0322] Photopolymerization initiator B is preferably a photoradical polymerization initiator, and more preferably a compound that breaks down into two or more free radicals by irradiation with ultraviolet or visible light.

[0323] Photopolymerization initiator B can be selected by measuring absorbance to identify compounds with appropriate absorption characteristics. Specifically, it can be selected from compounds that meet one or more of the following conditions: when dissolved at a concentration of 0.1% by mass in a solvent (such as acetonitrile or toluene) that does not have maximum absorption in the 300–500 nm wavelength region, it has an absorbance of 0.5 or more at a wavelength of 365 nm, an absorbance of 0.5 or more at a wavelength of 385 nm, and an absorbance of 0.5 or more at a wavelength of 405 nm.

[0324] As the photopolymerization initiator B, it is preferably selected from one or more of acylphosphine oxide compounds, diaceticolide compounds, and α-aminoalkylphenyl ketone compounds due to its excellent reaction rate and heat resistance after curing. These compounds tend to have absorption wavelengths in the range of about 440 nm or less, and are preferred because they have low absorbance at the wavelength of light used in the process of irradiating the temporary fixing layer with a laser. That is, the above-mentioned photopolymerization initiator B is a photopolymerization initiator capable of initiating free radical polymerization under longer wavelengths of light. Therefore, the difference between the wavelength of the irradiation light used to cure the temporary fixing composition and the wavelength of the laser used to decompose the temporary fixing layer can be increased. Furthermore, oxime ester compounds can also be selected as the photopolymerization initiator B.

[0325] Examples of acylphosphine oxide compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyl diphenylphosphine oxide. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.

[0326] Examples of titanium-based compounds include bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrolo-1-yl)-phenyl)titanium.

[0327] Examples of α-aminoalkylphenyl ketone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one and 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholino-4-ylphenyl)-butane-1-one.

[0328] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyl oxime and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime). Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] ethyl ketone 1-(O-acetyl oxime) is preferred.

[0329] From the viewpoint of exhibiting high absorption in the 365–405 nm wavelength region, the preferred photopolymerization initiator B is 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl] acetone 1-(O-acetyl oxime), 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyl oxime, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and 2,4,6-trimethylbenzoyl diphenylphosphine oxide, with bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide being more preferred.

[0330] In addition, bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl)titanium, which exhibits absorption in the longer wavelength range of 400–500 nm, is also preferred.

[0331] The content of photopolymerization initiator B relative to 100 parts by mass of the total amount of polymerizable compound A is preferably 0.01 to 10 parts by mass, 0.01 to 5.0 parts by mass, 0.1 to 3.0 parts by mass, or 0.5 to 1.5 parts by mass. When the content of photopolymerization initiator B is within the above range, it tends to further improve the adhesion of the temporary fixing layer formed using the temporary fixing composition.

[0332] 1.5.3. Other components

[0333] The temporary fixation composition may contain components other than polymerizable compound A and photopolymerization initiator B. Examples of such components include compounds that are not polymerizable compounds, have aromatic rings, or have hydrocarbon chains with three or more carbon atoms.

[0334] 2. Uses

[0335] The temporary fixing composition of this embodiment can preferably be used in a wafer manufacturing method to temporarily fix a wafer to a support member. The temporary fixing composition is preferably coated on the wafer surface to temporarily fix the wafer to the support member for processing the back side of the wafer. Since the temporary fixing composition of this embodiment has high laser ablation resistance, it can preferably be used to manufacture thin wafers with a thickness of several hundred μm. Furthermore, the temporary fixing composition of this embodiment is less likely to produce cured residue, thus suppressing traces of the temporary fixing layer even when a temporary fixing layer is formed on the wafer surface. Therefore, the temporary fixing composition of this embodiment can preferably be used for back side processing of thin wafers.

[0336] 3. Chip manufacturing methods

[0337] like Figure 2 As shown, the wafer manufacturing method of this embodiment includes: a step of bonding the wafer to a support member via the temporary fixing composition of this embodiment (hereinafter referred to as bonding step S0); a step of curing the temporary fixing composition by irradiating it with ultraviolet light to form a temporary fixing layer, and bonding the wafer to the support member via the temporary fixing layer (hereinafter referred to as curing step S1); a step of processing the wafer (hereinafter referred to as processing step S2); a step of irradiating the temporary fixing layer with a laser (hereinafter referred to as laser irradiation step S3); and a step of peeling the support member from the wafer at the interface of the temporary fixing layer (hereinafter referred to as peeling step S4).

[0338] In the bonding process S0, the wafer is bonded to the support member. The wafer is the substrate to be processed, such as a silicon substrate. Furthermore, the support member is preferably a support member that can transmit at least ultraviolet light, such as a glass plate.

[0339] The bonding method in bonding process S0 is not particularly limited, but it is preferable to apply the temporary fixing composition of this embodiment to one side of the wafer or support member and then bond another substrate.

[0340] As a coating method for temporary fixing compositions, known coating methods such as spin coating, screen printing, and various coating machines can be used, but spin coating is preferred. Spin coating refers to a method in which, for example, a temporary fixing composition as a liquid composition is dropped onto a wafer or support member, and the composition is coated onto the surface of a substrate by rotating the wafer or support member at a specified rotation speed.

[0341] In the curing step S1, the temporary fixing composition is cured by irradiating it with ultraviolet light, thus bonding the wafer to the support member. By using a transparent substrate that transmits at least ultraviolet light as at least one of the wafer and the support member, the temporary fixing composition can be easily irradiated with ultraviolet light. When an ultraviolet-transmitting substrate is used as the support member, ultraviolet light can be irradiated from the support member side. Examples of transparent substrates include inorganic substrates such as crystal, glass, quartz, calcium fluoride, and magnesium fluoride, as well as organic substrates such as plastics, but inorganic substrates are preferred.

[0342] The wavelength of the ultraviolet light can be appropriately selected according to the type of photopolymerization initiator B, for example, within the range of 350–405 nm. Preferably, the energy of the ultraviolet light within the 350–405 nm range is, for example, 1–20000 mJ / cm². 2 The preferred value is 1000–10000 mJ / cm². 2 Irradiation is performed in this manner.

[0343] In processing step S2, the surface of the wafer opposite to the surface to which the support member is attached is processed. Examples of such processing include insulating film formation, circuit formation, ion implantation, and thinning by grinding / polishing. The processing steps may include, for example, a thinning step by grinding / polishing, and a step including at least one of insulating film formation, circuit formation, and ion implantation. Insulating film formation, circuit formation, and ion implantation may be performed, for example, at high temperatures of 170–300°C.

[0344] Laser irradiation step S3 is a step in which a laser is irradiated onto the temporary fixing layer, which is a cured temporary fixing composition, to decompose the temporary fixing layer. The wavelength of the laser is preferably 350 to 385 nm. The laser can irradiate from the wafer side or the support member side, but irradiation from the support member side is preferred. As mentioned above, when the temporary fixing composition contains an aromatic ring bonded to heteroatoms, it tends to absorb laser energy more easily in the laser irradiation step.

[0345] In the stripping process S4, the support member is peeled from the wafer at the interface of the temporary fixing layer. In the laser irradiation process, the temporary fixing layer decomposes, generating gas from the decomposition components. The adhesion between the temporary fixing layer and the wafer or support member decreases, thereby allowing the wafer to be peeled from the support member.

[0346] The wafer manufacturing method of this embodiment preferably includes a step (hereinafter referred to as removal step S5) to remove the temporary fixing layer after laser irradiation from the wafer peeled off from the self-supporting member. By performing the removal step, the temporary fixing layer can be sufficiently removed even if it remains on the wafer.

[0347] The removal process is not particularly limited, as long as it removes the temporary fixing layer remaining on the wafer. For example, a method could be used where adhesive tape is applied to a wafer with residual temporary fixing layer, and then the tape is peeled off the wafer. In this method, the remaining temporary fixing layer is attached to the adhesive tape, so it can be removed along with the tape when peeling it off the wafer. For example, cutting tape used in the dicing process of semiconductor, electronic component, and optical component manufacturing can be used to fix workpieces.

[0348] Provided there is no contradiction, the temporary fixation composition of the second embodiment can possess the characteristics of the temporary fixation composition of the first embodiment.

[0349] Example

[0350] The present invention will be described in more detail below through embodiments, but the present invention is not limited to the following embodiments.

[0351] [Example A]

[0352] 1.1. Raw materials

[0353] The following compound is used as polymeric compound A.

[0354] 1.1.1. Polymerizable compound A1

[0355] • A1-1: Multifunctional acrylate polymer (weight average molecular weight 72,000, hydrocarbon long chain equivalent: 154.2 g / mol)

[0356] • A-DOD-N: 1,10-Decanediol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-DOD-N", R=-(CH2) in the structural formula described below) 10 - (Hydrocarbon long-chain equivalent: 282.4 g / mol)

[0357] HBPE-4: Ethylene oxide modified hydrogenated bisphenol A diacrylate (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., "HBPE-4", in the structural formula described below, m+n=4, hydrocarbon long chain equivalent: 524.7 g / mol)

[0358] •ISTA: Isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "ISTA", hydrocarbon long chain equivalent: 324.5 g / mol)

[0359] 1.1.2. Polymer compound A2

[0360] • A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "NK Ester A-BPEF-2", aromatic ring equivalent: 136.7 g / mol)

[0361] ·RUVA-93: 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole (manufactured by Otsuka Chemical Co., Ltd., "RUVA-93", aromatic ring equivalent: 160.7 g / mol)

[0362] ·DAINSORB P-66: 2,2'-Dihydroxy-4,4'-Diacryloxybenzophenone (manufactured by Yamato Kasei Corporation, "DAINSORB P-66", aromatic ring equivalent: 221 g / mol)

[0363] 1.1.3. Polymerizable compound A3

[0364] M-113: Nonylphenol ethylene oxide modified acrylate (manufactured by Toa Synthetic Co., Ltd., "Aronix M-113", n=4 in the structural formula below, hydrocarbon long chain equivalent: 386.6 g / mol, aromatic ring equivalent: 386.6 g / mol)

[0365] The following compound is used as photopolymerization initiator B.

[0366] • Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Omnirad 819", aromatic ring equivalent: 137.5 g / mol)

[0367] The structural formula of the above compound is shown below.

[0368]

[0369] 1.2. Preparation of the composition for temporary fixation

[0370] As shown in Table 2, for the examples and comparative examples, the materials were heated and mixed at 60°C to obtain a homogeneous liquid composition.

[0371]

[0372] 1.3. Physical property determination of the composition for temporary fixation

[0373] (Viscosity)

[0374] The viscosity of each composition was determined using the following method. The results are shown in Table 2.

[0375] Measuring apparatus: Type E viscometer DV3T-HB (manufactured by Eiko Seiki Co., Ltd.)

[0376] Measurement fixture: Conical plate CPA-40Z (manufactured by Eiko Seiki Co., Ltd.)

[0377] Measurement temperature: 23℃

[0378] Rotational speed: 10 rpm (500 mPa·s ~ 2500 mPa·s); 2 rpm (2501 mPa·s ~ 10000 mPa·s)

[0379] 1.4. Determination of peel strength

[0380] The peel strength X under heat treatment was determined by the following steps (i) to (iv). The results are shown in the “Heating” column of Table 3.

[0381] (i) The temporary fixing composition of the examples or comparative examples was spin-coated to a thickness of 70 μm onto a test substrate (aluminum-coated silicon substrate, polyimide-coated silicon substrate, or silicon substrate). After being bonded to a glass plate, the temporary fixing composition was photocured to form a coating film. The photocuring conditions were: curing wavelength 405 nm, illuminance 350 mW / cm². 2 Cumulative radiation dose: 5600 mJ / cm 2 It should be noted that the following materials are used for each substrate.

[0382] Aluminum-coated silicon substrate: Ti / Al film manufactured by Seiren KST (bottom Ti film 50μm, top Al film 100μm).

[0383] Polyimide-coated silicon substrate: A wafer with a 5μm non-photosensitive polyimide film manufactured by Seiren KST.

[0384] Silicon substrate: P-type manufactured by Silicon Technology <100> (Crystal axis) TTV specification wafer.

[0385] (ii) The test substrate with the coating film formed was heated at 175°C for 30 minutes.

[0386] (iii) The test substrate with the coating was irradiated with an energy density of 920 mJ / cm² under the conditions of wavelength 355 nm, frequency 40 kHz, spot diameter 150 μm, and pulse energy 165 μJ. 2 After laser treatment, the glass plate is peeled off. The laser is applied in a manner that scans the entire surface of the test substrate.

[0387] (iv) Apply release tape to the coating and make cuts on both the tape and the cured material with a peel width of 20 mm. Then, stretch the tape with the cured material attached under the conditions of 180 degrees in the peel direction, a peel width of 20 mm, a peel speed of 120 mm / min, and a temperature of 25°C, and measure the peel strength when the coating is peeled from the test substrate. Calculate the average value of 5 measurements. The measurement conditions are as follows.

[0388] Device: Tensilon RTG1210A

[0389] Tape: Eleclip Tape P Tape (Made by Denka)

[0390] Peeling direction: 180 degrees

[0391] Peel width: 20mm

[0392] Peeling speed: 120mm / min

[0393] Temperature: 25℃

[0394] Except for omitting the above-described step (ii), the peel strength Y was measured without heat treatment, in the same manner as the peel strength X. The results are shown in the "Unheated" column of Table 3.

[0395] 1.5. Residual Evaluation

[0396] The temporary fixation composition of the examples or comparative examples was spin-coated to a thickness of 70 μm onto a 4-inch patterned wafer (10 cm in diameter × 0.47 mm in thickness). After being bonded to a glass plate, the temporary fixation composition was photocured to form a test piece. The photocuring conditions were: curing wavelength 405 nm, illuminance 350 mW / cm². 2 Cumulative radiation dose: 5600 mJ / cm 2 Then, the test piece was placed on a hot plate heated to 175°C and subjected to a heat treatment for 30 minutes.

[0397] The pattern of the patterned chip is as follows: the aluminum portion consists of rounded rectangles, each 4mm square, spaced 1mm apart, surrounded by a polyimide portion. In this pattern, the aluminum portion accounts for 64% of the total area, and the polyimide portion accounts for 36%.

[0398] Next, the test piece was irradiated with an energy density of 920 mJ / cm² under the conditions of a wavelength of 355 nm, a frequency of 40 kHz, a spot diameter of 150 μm, and a pulse energy of 165 μJ. 2 After laser treatment, the glass plate is peeled off. The laser is applied in a manner that scans the entire surface of the test substrate.

[0399] Next, release tape was applied to the temporary fixing layer. The tape with the temporary fixing layer attached was stretched under the following conditions: 180 degrees in the peeling direction, 20 mm peeling width, 120 mm / min peeling speed, and 25°C, to peel the temporary fixing layer off the test substrate. The residual rate (area %) was calculated from the remaining area of ​​the temporary fixing layer (residual rate is denoted in the table). The results are shown in Table 3.

[0400]

[0401] [Example B]

[0402] 2.1. Raw materials

[0403] The following compound is used as polymeric compound A.

[0404] 2.1.1. Polymerizable compound A1

[0405] • A1-1: Multifunctional acrylate polymer (weight average molecular weight 72,000, hydrocarbon long chain equivalent: 154.2 g / mol)

[0406] • A-DOD-N: 1,10-Decanediol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-DOD-N", R=-(CH2) in the structural formula described below) 10 - (Hydrocarbon long-chain equivalent: 282.4 g / mol)

[0407] HBPE-4: Ethylene oxide modified hydrogenated bisphenol A diacrylate (manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., "HBPE-4", in the structural formula described below, m+n=4, hydrocarbon long chain equivalent: 524.7 g / mol)

[0408] • A-PTMG65: Polytetramethylene glycol diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-PTMG65", hydrocarbon long chain equivalent: 86.1 g / mol)

[0409] HX620: Caprolactone-modified neopentyl glycol diacrylate of hydroxypentylene glycol (manufactured by Nippon Kayaku Co., Ltd., "Kayarad HX-620", the structural formula described below has m+n=4, the left and right bonding sites are connected, hydrocarbon long chain equivalent: 111.4 g / mol)

[0410] •ISTA: Isostearyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., "ISTA", hydrocarbon long chain equivalent: 324.5 g / mol)

[0411] 2.1.2. Polymerizable compound A2

[0412] • A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "NK Ester A-BPEF-2", aromatic ring equivalent: 136.7 g / mol)

[0413] ·RUVA-93: 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole (manufactured by Otsuka Chemical Co., Ltd., "RUVA-93", aromatic ring equivalent: 160.7 g / mol)

[0414] P-66: 2,2'-Dihydroxy-4,4'-Diacryloxybenzophenone (manufactured by Yamato Kasei Corporation, "DAINSORBP-66", aromatic ring equivalent: 221 g / mol)

[0415] 2.1.3. Polymerizable compound A3

[0416] • ABE300: Ethoxylated bisphenol A diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "NK EsterABE-300", in the structural formula described below, R=-CH2CH2O-, m+n=3, hydrocarbon long chain equivalent: 468.5 g / mol, aromatic ring equivalent: 234.3 g / mol)

[0417] • A-BPE-2: Ethoxylated bisphenol A diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "NK Ester A-BPE-2", in the structural formula described below, R=-CH2CH2O-, m=n=1, hydrocarbon long chain equivalent: 424.5 g / mol, aromatic ring equivalent: 212.2 g / mol)

[0418] • A-BPE-10: Ethoxylated bisphenol A diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "NK Ester A-BPE-10", in the structural formula described below, R=-CH2CH2O-, m+n=10, hydrocarbon long chain equivalent: 776.9 g / mol, aromatic ring equivalent: 388.5 g / mol)

[0419] M-113: Nonylphenol ethylene oxide modified acrylate (manufactured by Toa Synthetic Co., Ltd., "Aronix M-113", n=4 in the structural formula below, hydrocarbon long chain equivalent: 386.6 g / mol, aromatic ring equivalent: 386.6 g / mol)

[0420] 2.1.4. Polymerizable compound A4

[0421] • A-DCP: Tricyclodecanedimethyl diacrylate (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-DCP")

[0422] The following compound is used as photopolymerization initiator B.

[0423] • Omnirad 819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Omnirad 819", aromatic ring equivalent: 137.5 g / mol)

[0424] The structural formula of the above compound is shown below.

[0425]

[0426] 2.2. Preparation of the composition for temporary fixation

[0427] As shown in Tables 5-7, for each embodiment and comparative example, the materials were heated and mixed at 60°C to obtain a homogeneous liquid composition. In Tables 5-7, the concentrations of aromatic rings and hydrocarbon chains with 3 or more carbon atoms (denoted as "hydrocarbon long chain concentration") were calculated based on the aromatic ring equivalents and hydrocarbon chain equivalents and contents of the raw materials.

[0428] 2.3. Physical property determination of the composition for temporary fixation

[0429] (Viscosity)

[0430] The viscosity of each composition was determined using the following method. The results are shown in Tables 5–7.

[0431] Measuring apparatus: Type E viscometer DV3T-HB (manufactured by Eiko Seiki Co., Ltd.)

[0432] Measurement fixture: Conical plate CPA-40Z (manufactured by Eiko Seiki Co., Ltd.)

[0433] Measurement temperature: 23℃

[0434] Rotational speed: 10 rpm (500 mPa·s ~ 2500 mPa·s); 2 rpm (2501 mPa·s ~ 10000 mPa·s)

[0435] (Cross-linking density of the cured material)

[0436] To determine the crosslinking density of the cured products of each composition, the storage elastic modulus was measured according to the following method. Then, the storage elastic modulus of the rubbery flat region at 200°C was set as E' [Pa], and the gas constant was set as R = 8.31 × 10⁻⁶. 7 The crosslinking density was calculated using the following formula, with the absolute temperature set to T[K] and [Pa·L / (K·mol)]. The results are shown in Tables 5–7. Examples and comparative examples for which no measurements were performed are indicated by “-” in the tables.

[0437] Crosslinking density n = E' / 3RT

[0438] Measurement apparatus: RSA-3 (manufactured by TA Instruments)

[0439] Measurement mode: Tension

[0440] Measurement temperature: 23~250℃

[0441] Measurement frequency: 1Hz

[0442] Strain measured: 0.1%

[0443] Heating rate: 3℃ / min

[0444] Test piece: Temporary fixation composition measuring 0.5mm × 15mm × 0.07mm

[0445] Spacing between fixtures: 10mm

[0446] 2.4. Performance testing of compositions for temporary fixation

[0447] (Heat resistance evaluation)

[0448] Using the prepared temporary fixation composition, a 6-inch silicon wafer (10 cm in diameter × 0.63 mm in thickness) was bonded to a 6-inch glass support member (10 cm in diameter × 0.7 mm in thickness). During bonding, the thickness of the temporary fixation composition was adjusted to 70 μm. After bonding, a 405 nm wavelength UV LED was used at an illuminance of 100 mW / cm². 2 Irradiation time: 50 seconds; cumulative light intensity: 5000 mJ / cm² 2 The mixture was cured under the specified conditions, then placed on a hot plate heated to 175°C for 30 minutes to prepare evaluation test pieces. A temporary fixing composition was applied to the entire surface of the bonding area. The heat resistance was evaluated by visually observing the heated test pieces and assessing the presence of delamination at the adhesive interface. The presence of delamination at the adhesive interface is shown in Tables 5–7.

[0449] (Laser Peel Resistance Evaluation) The evaluation test piece was prepared in the same manner as the heat resistance evaluation. A 355nm UV laser was irradiated from the glass support side of the resulting 6-inch test piece, scanning the entire surface of the piece, onto a circular area with a diameter of 160mm centered on the test piece. The laser irradiation conditions were: frequency 40kHz, spot diameter 150μm, pulse energy 165μJ, and irradiation energy density 920mJ / cm².

[0450] The laser-irradiated test piece was placed on an adsorption stage (porous chuck type) with the silicon wafer facing down and fixed in place. Adsorption arms with three 10mm diameter suction cups were attached to the test piece in this state (on the glass support side). The glass support component was peeled off by vertically pulling the adsorption arms upwards at a speed of 0.5mm / s, and the laser peeling performance was evaluated. The presence or absence of laser peeling performance is shown in Tables 5-7. Peeling was indicated as "acceptable," and peeling was not indicated as "unacceptable."

[0451] (Residual evaluation)

[0452] In the laser peelability evaluation, for test pieces where the wafer has been peeled from the support member, the residue of the temporary fixing layer is evaluated as follows. Adhesive tape is applied to the side of the wafer with the temporary fixing layer removed from the support member, and cuts are made on the tape and the cured material with a peel width of 20 mm. Then, the tape with the cured material attached is stretched and peeled off. The average of five measurements is calculated. Simultaneously, the residue rate (area %) of the cured material after tape removal is calculated (residue rate is denoted in the table). The results are shown in Tables 5–7.

[0453] Device: Tensilon RTG1210A

[0454] Tape: Eleclip Tape P Tape (Made by Denka)

[0455] Peeling direction: 180 degrees

[0456] Peel width: 20mm

[0457] Peeling speed: 120mm / min

[0458] Temperature: 25℃

[0459]

[0460]

[0461]

Claims

1. A composition, The peel strength X was measured by the following method (X) using polyimide as the test substrate. PI Below 0.50 N / mm The peel strength Y was measured by the following method (Y) using polyimide as the test substrate. PI It is above 0.10 N / mm. The peel strength X PI With the peel strength Y PI The ratio of X PI / Y PI Below 1.5; (X) The peel strength is determined by the following steps (i) to (iv): (i) The composition is coated onto a test substrate with a thickness of 70 μm, and after being bonded to a glass plate, the composition is photocured to form a coating film. (ii) The test substrate with the coating formed is heated at 175°C for 30 minutes. (iii) The coating is irradiated at a wavelength of 355 nm and a frequency of 40 kHz with an energy density of 920 mJ / cm². 2 After the laser beam is applied, the glass plate is peeled off. (iv) Adhesive tape was applied to the coating film, and the peel strength was measured when the coating film was peeled from the test substrate under the conditions of peel direction of 180 degrees, peel width of 20 mm, peel speed of 120 mm / min and temperature of 25°C. The average value of 5 measurements was taken. (Y) In the above-described test method (X), the peel strength is measured without performing the above-described procedure (ii).

2. The composition according to claim 1, wherein, The ratio X PI / Y PI The value ranges from 0.30 to 1.

0.

3. The composition according to claim 1, wherein, The peel strength X measured by the aforementioned method (X) using aluminum as the test substrate Al Below 0.60 N / mm The peel strength Y, measured by the aforementioned method (Y) using aluminum as the test substrate. Al It is above 0.10 N / mm. The peel strength X Al With the peel strength Y Al The ratio of X Al / Y Al It is below 2.

0.

4. The composition according to claim 3, wherein, The ratio X Al / Y Al It ranges from 1.0 to 2.

0.

5. The composition according to claim 3, wherein, The peel strength X PI With the peel strength X Al The ratio of X PI / X Al The value is 0.10 to 0.

50.

6. The composition according to claim 1, wherein, The peel strength X measured by the aforementioned measurement method (X) using silicon as the test substrate Si Below 0.50 N / mm The peel strength Y, measured by the aforementioned method (Y) using silicon as the test substrate. Si It is above 0.10 N / mm. The peel strength X Si With the peel strength Y Si The ratio of X Si / Y Si It is below 1.

6.

7. The composition according to claim 6, wherein, The ratio X Si / Y Si The value ranges from 0.3 to 1.

2.

8. The composition according to claim 1, comprising polymerizable compound A and photopolymerization initiator B.

9. The composition according to claim 8, wherein, Polymer compound A contains: Polymerizable compound A1 having a hydrocarbon chain with 3 or more carbon atoms, and A2 is a polymeric compound with an aromatic ring.

10. The composition according to claim 9, wherein, The polymeric compound A1 contains (meth)acrylates with a functional group equivalent of less than 200 g / mol of hydrocarbon chains having 3 or more carbon atoms.

11. The composition according to claim 9, wherein, The polymeric compound A1 comprises a (meth)acrylate having a hydrocarbon chain having 8 or more carbon atoms.

12. The composition according to claim 9, wherein, As the polymeric compound A2, it comprises (meth)acrylate with an aromatic ring equivalent of less than 200 g / mol.

13. The composition according to claim 9, wherein, The content of the polymeric compound A1 is 50 to 98 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

14. The composition according to claim 9, wherein, The content of the polymeric compound A2 is 2 to 50 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

15. The composition according to claim 8, wherein, The content of the photopolymerization initiator B is 0.01 to 10 parts by mass relative to 100 parts by mass of the total amount of polymerizable compound A.

16. A composition for temporary fixation, comprising the composition according to any one of claims 1 to 15.

17. A method for manufacturing a wafer, comprising: The process of bonding a wafer to a support member using the temporary fixing composition as described in claim 16; The process of curing the temporary fixation composition by irradiating it with ultraviolet light to form a temporary fixation layer, and then bonding the wafer to the support member through the temporary fixation layer; The process of heat-treating the wafer; The process of irradiating the temporary fixation layer with laser; and The process of peeling the support member from the wafer at the interface of the temporary fixing layer.

18. The manufacturing method according to claim 17, wherein, The process further includes the step of removing the temporary fixing layer after laser irradiation from the wafer.

19. A composition having a peel strength X determined by the following method (X) using polyimide as a test substrate. PI The peel strength Y, measured by the following method (Y) using polyimide as the test substrate, is compared with the peel strength Y. PI The ratio of X PI / Y PI Below 1.5; (X) The peel strength is determined by the following steps (i) to (iv): (i) The composition is coated onto a test substrate with a thickness of 70 μm, and after being bonded to a glass plate, the composition is photocured to form a coating film. (ii) The test substrate with the coating formed is heated at 175°C for 30 minutes. (iii) The coating is irradiated at a wavelength of 355 nm and a frequency of 40 kHz with an energy density of 920 mJ / cm². 2 After the laser beam is applied, the glass plate is peeled off. (iv) Adhesive tape was applied to the coating film, and the peel strength was measured when the coating film was peeled from the test substrate under the conditions of peel direction of 180 degrees, peel width of 20 mm, peel speed of 120 mm / min and temperature of 25°C. The average value of 5 measurements was taken. (Y) In the measurement method (X), the peel strength is measured without performing the step (ii).

20. A composition comprising a polymerizable compound A and a photopolymerization initiator B, The concentration of hydrocarbon chains with 3 or more carbon atoms is above 2.80 mmol / g. The concentration of aromatic rings is above 0.60 mmol / g.

21. The composition according to claim 20, wherein, The crosslinking density of the cured material after ultraviolet irradiation was 0.10 mmol / cm³. 3 above.

22. The composition according to claim 20, wherein, The ratio of the concentration of the hydrocarbon chain with 3 or more carbon atoms to the concentration of the aromatic ring is 1.5 or more.

23. The composition according to claim 20, wherein, The polymeric compound A comprises at least one selected from polymeric compound A1 having a hydrocarbon chain with 3 or more carbon atoms, polymeric compound A2 having an aromatic ring, and polymeric compound A3 having a hydrocarbon chain with 3 or more carbon atoms and an aromatic ring.

24. The composition according to claim 23, wherein, For at least one of the polymerizable compounds A1 and A3, there is a (meth)acrylate containing a hydrocarbon chain with a carbon number of 3 or more that has a functional group equivalent of 200 g / mol or less.

25. The composition according to claim 23, wherein, At least one of the polymeric compounds A1 and A3 comprises a (meth)acrylate having a hydrocarbon chain having 8 or more carbon atoms.

26. The composition according to claim 23, wherein, At least one of the polymeric compounds A2 and A3 contains a (meth)acrylate with an aromatic ring equivalent of less than 200 g / mol.

27. The composition according to claim 23, wherein, The content of the polymeric compound A1 is 50 to 98 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

28. The composition according to claim 23, wherein, The content of the polymeric compound A2 is 2 to 50 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

29. The composition according to claim 23, wherein, The content of the polymeric compound A3 is 0 to 48 parts by mass relative to the total amount of polymeric compound A (100 parts by mass).

30. The composition according to claim 20, wherein, The content of the photopolymerization initiator B is 0.01 to 10 parts by mass relative to 100 parts by mass of the total amount of polymerizable compound A.

31. The composition according to claim 20, wherein, The polymerizable compound A includes monofunctional polymerizable compounds and polyfunctional polymerizable compounds. The content of the monofunctional polymeric compound is 0.01 to 60 parts by mass relative to the total amount of the polyfunctional polymeric compound per 100 parts by mass.

32. The composition according to claim 20, wherein, The viscosity at 23℃ is 500 mPa·s to 10000 mPa·s.

33. A temporary fixation composition comprising any one of claims 20 to 32.

34. A method for manufacturing a wafer, comprising: The process of bonding a wafer to a support member using the temporary fixing composition as described in claim 33; The process of curing the temporary fixation composition by irradiating it with ultraviolet light to form a temporary fixation layer, and then bonding the wafer to the support member through the temporary fixation layer; The process of processing the wafer; The process of irradiating the temporary fixation layer with laser; and The process of peeling the support member from the wafer at the interface of the temporary fixing layer.

35. The manufacturing method according to claim 34, wherein, The process further includes the step of removing the temporary fixing layer after laser irradiation from the wafer.

Citation Information

Patent Citations

  • Resin composition for cladding optical fiber

    JP1986031330A

  • Resin and resin composition for sealant

    JP1986207478A

  • Photocurable urethane acrylate oligomer and photocurable composition

    JP1997040741A

  • Thermally bondable film and processing material to be covered

    JP1998278207A

  • Composition

    WO2021235406A1